Drought weakens greenhouse gas sink of global wetlands - Longxin Qiao; Xinxin Wang; Hongyang Chen; Jihua Wu; Xiangming Xiao; Ming Nie; Rui-Ting Ju; Yuhan Zheng; Xi Zhang; Qiang He; Xutong Ru; Lijuan Cui; et al. (Environmental Impact Assessment Review, 2027)

In situ sludge reduction induced by graphene oxide: Mechanistic insights into metabolic uncoupling, maintenance energy and cryptic growth - Yaodong Wu; Yiqi Sun; Rui Yu; Yanan Cui; Fan Yang; Jun Li; Zehao Zhang (Bioresource Technology, 2026)

Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

Facilitating component separation and cascade resource utilization of sewer sludge using alkaline plant ash - Jiangbo Ding; Lei An; Yunfeng Liu; Hongjun Cui; Jun Wang; Rui Ma; Jinsuo Lu; Heliang Pang (Water Research, 2026)

Dual roles of static magnetic field on enhancing sulfamethoxazole biodegradation and preventing antibiotic resistance genes transfer in halotolerant fungal-bacterial sludge treating saline aquaculture wastewater - Zhen-Ying Li; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Yuan Sui (Bioresource Technology, 2026)

Investigation of electrode-free, room temperature, flexible NH3 sensors with high stability and sensitivity using MXene@PANI-MWCNTs ink - Jiahui Zheng; Bochao Ma; Xiaoqing Cui; Rui Wang; Li An; Bin Guo; Hongyan Zhang (Analytica Chimica Acta, 2026)

A cascaded signal amplification strategy combining Au@Cu2O core-shell nanozymes and CRISPR-Cas12a self-cycling for ultrasensitive colorimetric detection of miRNA-21 - Jiaxin Li; Mingjia Yuan; Xueting Cui; Yingqiao Ding; Mengliu Yang; Rui Liu; Ling Li (Analytica Chimica Acta, 2026)

Enhancing resistance against white spot syndrome virus in Litopenaeus vannamei via recombinant Lactobacillus acidophilus through modulation of gut microbiota function - Hang Zhang; Wei Liu; Yi-Ning Cui; Pei-Min He; Ji-shun Yang; Rui Jia (Aquaculture, 2026)

The safety evaluation of the pVAX-ROP27 DNA vaccine against Eimeria tenella - Xiaoling Lv; Baojie Li; Xuan Chang; Wenrui Zhao; Menggang Li; Jiaqi Zhao; Kewei Dou; Zhibin Niu; Rui Bai; Li Zhang; Xiaozhen Cui (Veterinary Immunology and Immunopathology, 2026)

Delivery systems derived from egg yolk components: Carrier types, enhancement methods, and applications - Shuze Ren; Rui Cui; Akihiro Handa; Kazuhiro Isobe; Xi Huang (Trends in Food Science & Technology, 2026)

Preservative prospect of Ugni candollei (Barnéoud) O.Berg, an underexploited edible berry tree from Chile - Rui Fang; Gabin Bitchagno; Max Cui; Paula Coates; James Venison; Andrew Peplow; Debbie Mulligan; Monique S.J. Simmonds (Phytochemistry, 2026)

Catalytic ozonation with N, S co-doped sludge biochar for decontamination: Performance and mechanistic insights - Xinyi Tao; Weiwei Chen; Xuehong Fan; Rui Hu; Xuejian Wang; Shiquan Sun; Yu-Hong Cui; Zheng-Qian Liu (Journal of Environmental Chemical Engineering, 2026)

Research on the application of metal oxides in flue gas mercury removal enabled by machine learning - Yang Sun; Miao An; Rui He; Cui Jie; Jiaoyu Yang; Mi Liu; Zhiling Qian; Jing Yin; Yanxiao Cao; Hongcheng Ruan; Honghu Li (Journal of Environmental Chemical Engineering, 2026)

Endogenous impurity regulation in solid waste-derived hydroxyapatite: From single-phase defects to in-situ multiphase reconstruction - Qingning Bai; Tongyu Liu; Xiaoyan Zhao; Zhiyu Chen; Shuo Cui; Jiayu Feng; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia; Fang Wang (Journal of Environmental Chemical Engineering, 2026)

Denitrification performance in low C/N water by aerobic denitrifying bacterial consortia coupled with biochar: Effects of pyrolysis temperature and dissolved oxygen - Rui Huo; Yiling Di; Wanying Li; Chenbin Wu; Yingchao Cui; Shilei Zhou (Journal of Environmental Chemical Engineering, 2026)

Electronic, optical and mechanical properties, and photocatalytic water splitting of Janus ZrHfCO2 under biaxial strain: First-principles prediction - Rui-Wen Yan; Hao Zhang; Xiao-Hong Li; Rui-Zhou Zhang; Hong-Ling Cui (Journal of Environmental Chemical Engineering, 2026)

Asymmetric ceramic membranes fabricated using equal amounts of red mud and fly ash for oil-in-water emulsion separation - Rui Zhang; Wenjuan Chen; Siqi Lan; Hongsen Lv; Yali Wang; Qunyan Li; Suping Cui; Qi Wei; Zuoren Nie (Journal of Environmental Chemical Engineering, 2026)

Enhanced photodynamic inactivation against Listeria monocytogenes under blue light mediated by carbon dots derived from ‘Shatian’ pomelo peels for ready-to-eat sausage preservation - Ce Shi; Rui Yang; Xinyu Huang; Ziwei Liang; Layla A. Alahmari; Maha Abdullah Alwaili; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2026)

Spatio-temporal-functional assembly of Daqu microbiome: Mechanistic insights and quality improvement - Rui Ma; Xiaojie Nan; Yanting Li; Yuanyu Su; Mingxia Cheng; Yujie Zhang; Yang Cui; Qiong Zhou; Jingang Gu; Shang Guo (Food Research International, 2026)

Effect of food components on arsenic metabolism by the gut microbiota using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME) - Yue Wu; Shimao Xiong; Xiyan Jiang; Peng Xiao; Fang Zhao; Rui Li; Syed Ali Hassan; Xiaolin Cai; Zhengyi Hu; Dennis Sandris Nielsen; Naiyi Yin; Yanshan Cui (Food Research International, 2026)

Streptomyces sp. G21 mitigates postharvest mango anthracnose by tuning ROS and phenylpropanoid metabolism - Yahui Cui; Jinhe Li; Jian Xu; Xiaolei Zhu; Muhammad Muzammal Aslam; Yuanzhi Shao; Rui Li; Wen Li (Food Research International, 2026)

The journey of fluxapyroxad, mandipropamid and mefentrifluconazole residues in two morphologically distinct chilli peppers: A comprehensive risk assessment from field to processing - Kai Cui; Rui Ni; Wanru Su; Liping Fang; Ruiyan Ding; Shuai Guan; Jingyun Liang; Jian Wang; Zhan Dong (Food Chemistry, 2026)

Machine learning models reveal the spatial distribution and key environmental drivers of Coilia nasus in East China Sea's coastal waters - Zeyu Xiao; Jiarong Shen; Haoran Wang; Rijin Jiang; Jianxiong Li; Rui Yin; Jiaying Zeng; Mingyuan Cui (Estuarine, Coastal and Shelf Science, 2026)

Upcycling hazardous electric arc furnace dust into defect-rich ZnO/ZnFe2O4 heterojunction for in situ H2O2 electrogeneration and water purification - Lijuan Jia; Bo Liu; Guoxing Mu; Yiqiang Ji; Fang Wang; Rui Cao; Ping Ning; Shuo Cui; Jiayu Feng (Chemical Engineering Journal, 2026)

Disintegrated halophilic aerobic granular sludge restoration using zinc oxide nanoparticles: synergistic effects of fungal toxicity inhibition and extracellular polymeric substances production - Ya-Nan Mi; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Zhen-Ying Li; Xu-Zhen Liu; Tong Ren (Bioresource Technology, 2026)

Triply activated localized DNA circuit based on dual enzyme-guaranteed and analyte-stimulated strategy for robust tumor-cell-specific microRNA imaging - Yuanyuan Peng; Xiaoyu Wang; Wanling Cui; Rui Wang; Haiyan Zhao; Ning Zhang; Min Liu; Yushu Wu (Analytica Chimica Acta, 2026)

Rapid Screening of Bacterial Chemoeffectors of Pseudomonas parafulva Using a CheA ATPase Activity‐Based Assay - Rui Cui; Jie Li; Ni‐Ye You; Tino Krell; De‐Feng Li (Environmental Microbiology, 2026)
Bacterial chemotaxis enables cells to move in gradients of environmental signals that are sensed by chemoreceptors. A major limitation in the field consists currently in the lacking information on the signal(s) or chemoeffectors recognized by the majority of chemoreceptors, which in turn hampers understanding of how the environment has shaped chemotactic capabilities. A number of different approaches for signal identification have been reported that are often labour‐intensive. Here, we developed a straightforward NADH‐coupled CheA ATPase assay to systematically screen potential chemoeffectors. Obtained results are complemented with differential scanning fluorimetry and isothermal titration calorimetry analyses, as well as structural protein modelling to study the chemoreceptors of Pseudomonas parafulva PSR09‐11288. Using this integrated approach, we identified L‐malate, citrate, L‐glutamine, and L‐asparagine as chemoattractants and revealed that chemoreceptor B2J77_03605 specifically recognizes L‐malate and citrate, whereas chemoreceptor B2J77_13170 binds L‐glutamine and L‐asparagine. The universality of this approach is shown by the fact that both chemoreceptors belong to different families and possess sensor domains that belong to the HBM and dCache families, respectively. This pipeline is a scalable workflow for chemoeffector identification, permitting systematic exploration of bacterial chemotactic capabilities.

HtpsB, a type II histidine triad protein of Streptococcus suis, contributes to bacterial virulence and blood-brain barrier disruption - Jingyan Fan; Jinpeng Zhang; Baiyi Chen; Yixin Han; Hexiang Jiang; Simin Deng; Luqing Cui; Xiaolu Lai; Kalliopi Rantsiou; Luca Simone Cocolin; Rui Zhou; Houhui Song; et al. (Veterinary Microbiology, 2026)

A simple osmotic intervention suppresses nanoparticle-induced bacterial persistence during environmental disinfection - Rui Sun; Yijin Tian; Siyang Xue; Yueting Cui; Yunchen Zhao; Shuaishuai Li; Jiawei Yuan; Xuanxuan Zhang; Chengdong Zhang (Journal of Hazardous Materials, 2026)

Inner Helmholtz plane reconstruction-driven dynamic capture and conversion of crystalline water enables ultra-long cycle life of FeHCF cathodes - Rui Sun; Danyu Cui; Zijun Deng; Zhengyang Zhao; Zhe Cheng; Longqing Zhang; Yuhong Liang; Quanqiang Yuan; Chengcheng He; Yan Zhang; Qian Ning; Yang Ren; et al. (Chemical Engineering Journal, 2026)

Modification of Ce−Fe oxide by quenching induced trace Sn doping for accelerating chlorobenzene oxidation - Juexiu Li; Wenbo Xue; Huandan Cui; Yige Xi; Rui Zhao; Yin Liu; Zhongxian Song; Kajia Wei; Ziqiang Li; Chuanyi Fan; Kan Li; Jinping Jia (Chemical Engineering Journal, 2026)

Bioinspired core-shell structured electrospun fibers guide neural stem/progenitor cell lineage development for spinal cord injury repair - Jiaxin Chen; Zilong Rao; Rui Cui; Rongli Deng; Jing Zhou; Daping Quan; Xipeng Guan; Houqing Long; Ying Bai (Chemical Engineering Journal, 2026)

Wearable multifunctional conductive fabrics for integrated smart monitoring and protection of the human body - Miao Miao; Wendi Liu; Wuwei Bao; Rui Ma; Hao Yao; Zhenzhe Huang; Zixuan Lin; Ying Han; Wentao Shen; Yao Wang; Yifan Cui; Xinyang He (Chemical Engineering Journal, 2026)

Spatiotemporal dynamics of land degradation in the three gorges reservoir area and its coupling mechanisms with biodiversity and human activity intensity - Cuicui Ji; Hao Cui; Rui Ma; Dandan Ke; Xia Li; Fenglei Han; Xizeng Huang; Jie Liu; Gang Yang; Liejian Wang (CATENA, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

Corrigendum to “Investigation on unrecognized catalytic contributing role of chlorobenzene oxidation by iron ore in sintering process” [Process Safety and Environmental Protection 203 (2025) 107862] - Juexiu Li; Wenbo Xue; Huandan Cui; Xinrui Lei; Wenlong Zhou; Rui Zhao; Ziqiang Li; Chuanyi Fan; Zhongxian Song; Jinping Jia (Process Safety and Environmental Protection, 2026)

Initial exploration of the health effects on Qinghai-Tibetan Plateau yaks following short-term exposure to polystyrene microplastics: Analysis of rumen microbiota, host metabolism, antioxidant function and inflammatory responses - Penghu Zhang; Yanbing Zhu; Zhisheng Wang; Peiqiang Yu; Bai Xue; Lizhi Wang; Rui Hu; Huawei Zou; Yahui Jiang; Jianxing Xiao; Cui Tan; Fali Wu; et al. (Journal of Hazardous Materials, 2026)

Metabolic complementarity in LAB-yeast co-fermentation associates with enhanced ester aroma in cream cheese - Beibei Duan; Yueyue Zhou; Siyu Wang; Ling Yan; Yujie Lin; linze Li; Bin Xue; Rui Huang; Yipan Zhang; Yue Cui; Nan Wu; Xiangting Kong; et al. (Food Research International, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Using attapulgite to reduce nitrous oxide emissions in a post-wheat green manuring system under 30% fertilizer reduction - Xiaohong Mao; Heng Cui; Rui Liu; Jiudong Zhang; Aizhong Yu; Danna Chang; Weidong Cao (European Journal of Agronomy, 2026)

Identification of distributed heat sources intensities with deterministic flow fields in ventilated spaces - Yemin Liu; Xiaoliang Shao; Rui Wang; Xiaohe Tian; Huifang Fan; Jianeng Cui (Building and Environment, 2026)

Root-specific induction of the Na+ transporter TaHKT8-4D restricts shoot Na⁺ accumulation and confers differential salt tolerance in allohexaploid wheat genotypes - Minnan Pei; Juan Wang; Rui Cui; Yingna Feng; Yunhong Zhang; Ting Zhou; Yingpeng Hua (Plant and Soil, 2026)

Real-time sick fish detection system for aquaculture based on edge computing - Duanrui Wang; Fan Ge; Rui Xu; Xingyue Zhu; Hongjian Lv; Dianting Zeng; Meng Wu; Jiyang Yu; Weijian Cui; Qiwei Qin; Shaowen Wang; Yi Shi; et al. (Aquaculture, 2026)

Lycium barbarum glycopeptide promotes bone health in ovariectomized mice via PI3K-Akt activation and osteoclast suppression - Meng Gao; Kai He; Jiabao Wu; Jiahui Cui; Ning Wang; Rui Ding (Food Bioscience, 2026)

Generation and characterization of the monoclonal antibody against the heavy chain of American eel (Anguilla rostrata) IgM - Xiaolong Meng; Shuangshuang Cao; Hongjun Xie; Wenting Jiang; Rui Guo; Yuchen Zhuo; Qicheng Wang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2026)

Sericin-bioinspired nanoplatform prevents bisphosphonate-related osteonecrosis of the jaw: synergistic mitochondrial modulation and microenvironmental restoration - Zhuoya Cui; Yuanyang Li; Kehong Guo; Hanrui Liao; Zitong Xia; Tao Wang; Rui Cai; Yao Wang; Gang Tao; Dan Zhao (Chemical Engineering Journal, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Integrative Bioinformatics and Experimental Validation Identify LOX as a Glycolysis-Related Biomarker in Myocardial Ischemia–Reperfusion Injury - Liying Wang; Zhian Chen; Tianying Liu; Yan Cui; Rui Zhang; Yong Cui; Zhi Liu (Cardiovascular Toxicology, 2026)

Evaluation of liver toxicity in rats exposed to silver nanoparticles – Targeted metabolomics and histology based study - Su Rui; Wang Yueyang; Han Zezhou; Cui Yunlong; Li Jianguo (Toxicology and Applied Pharmacology, 2026)

Earthworms counteract drought-induced impairment of wheat performance at the jointing stage regardless of microplastic type - Ruixin Du; Hanwen Cui; Ying Liu; Rui Wu; Yi Zhang; Chuanxiong Huang; Conghui Liu; Jianglan Shi; Xiaohong Tian; Rui Yin (Journal of Hazardous Materials, 2026)

A Ca-MOF@COF composite and its in situ grown gel membrane for highly efficient capture of Cd2+ - Xue-Mei Liu; Chuang-Chuang Zhang; Kun Yang; Wei-Liang Jin; Guan-Lian Mo; Rui Liu; Hong-Xin Jiang; Hao-Jie Cui; De-Ming Kong (Journal of Cleaner Production, 2026)

A detoxifying multi-strain probiotic formula attenuates toxicity induced by heavy metals and phthalates - Rui Xiao; Yaqi Yu; Deshan Ning; Zehua Chen; Chuguang Ning; Leilei Yu; Shumao Cui; Jianxin Zhao; Gang Wang; Yong Zhou; Xing Jin (Food Research International, 2026)

Linking environmental concentrations to cytotoxic mechanisms in second-hand vapor exposure of electronic cigarette via an integrated approach for in vitro toxicity assessment - Tong Cui; Yanpeng Li; Rui Lu; Zhenyu Niu; Xingtao Jiang (Environmental Pollution, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Hydrogenophaga pseudoflava widely distributed in wastewater treatment plants exhibiting heterotrophic nitrification-aerobic denitrification: From characterization to genomics - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Jia-Ying Li; Ya-Nan Mi; Xin-Yu Gu (Bioresource Technology, 2026)

Automated annotation and optimization of multitask dataset for spacecraft - Shengyun Zhao; Linyan Cui; Rui Zhong (Advances in Space Research, 2026)

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

Shift in orbital-scale climate response under the coupling of ice sheet and monsoon during the Late Oligocene: Sedimentary records from the East China Sea Shelf Basin - Yingkun Cui; Fujie Jiang; Xianke He; Yichen Liu; Wenji Wang; Rui Zhang; Yinghui Liu; Zhuo Li; Zhenguo Qi; Bo Xu; Hang lv; Jiming Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Occurrence and dietary risk assessments of polyethoxylated tallow amine in soybeans - Xinru Cui; Zhenjun Liu; Rui Yang; Minjie Li; Xinru Guo; Zixuan Liu; Ziqian Xue; Bei Fan; Zehua Ke; Chunmei Li; Fengzhong Wang (Journal of Hazardous Materials, 2026)

Valorization of industrial carbide slag via microwave processing: A low-cost route to high-performance CaO-based CO2 sorbents - Fang Wang; Yi Dong; Shaojun Luo; Zixia Tian; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Futing Xia; Jiayu Feng; Lijuan Jia (Journal of Environmental Management, 2026)

Foliar silicon application enhances rare earth element accumulation in the hyperaccumulator Phytolacca americana - Rui-Qi Zhang; Cui-Ling Huang; Ling-Xiu Zhou; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Environmental Sciences, 2026)

Effective sequestration of phosphate by ultrasmall hydrated Zr(IV) oxide nanoparticles confined inside the PEI-crosslinked chitosan beads - Rui Ma; Xinjie Cui; Youyi Liu; Qianhui Xu; Weiwei Wang; Guangze Nie (Journal of Environmental Sciences, 2026)

Application of layered double hydroxides (LDHs) derived catalysts for selective catalytic reduction of NOx with NH3 - Tian-yu Lv; Zuo-lin Cui; Rui-tang Guo (Fuel, 2026)

Trade-offs between crop yield and soil organic carbon sequestration under straw return across cropping systems - Yufei Cui; Mengdi Yang; Xiao Yang; Rui Wang; Shengli Guo (Field Crops Research, 2026)

Performance enhancement of alkali-activated slag via in situ CO2 mineralization - Gao Rui; Xu Bingqi; Gao Weichen; Jiang Ping; Zhang Shiyu; Cui Kai; Zhao Yingliang (Sustainable Chemistry and Pharmacy, 2026)

CoTiO3 immobilized on nickel foam for degradation of levofloxacin via peroxymonosulfate activation: Electron transfer pathways and degradation mechanism - Zhonghua Mu; Peng Cui; Rui Gao; Jikai Liu; Wei Li; Yushu Zhang; Wenqiang Ma; Hairui Li; Shiqi Wu; Shuzheng Zhang; Zhaohui Wang; Lei Yang; et al. (Process Safety and Environmental Protection, 2026)

Mechanistic insights into vanillin's inhibitory effects on Fusarium oxysporum induced postharvest disease - Xinlin Liu; Jiakai He; Yahui Cui; Muhammad Muzammal Aslam; Jian Xu; Rui Li; Wen Li (Postharvest Biology and Technology, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Revisit the improvement of coagulation pretreatment on ozonation performance: The critical roles of HO• and O3 for effluent organic matter transformation and micropollutant degradation - Rui Hu; Hao-Tong Zheng; Boxi Tang; Jialing Tu; Yu-Hong Cui; Xuedong Zhai; Gang Wen; Zheng-Qian Liu (Journal of Cleaner Production, 2026)

Continental weathering and redox dynamics modulated marine phosphorus availability during the Sturtian deglaciation - Ruru Li; Jun Hu; Sanzhong Li; Yuhao Li; Zheng Qin; Rui Dong; Huan Cui; Xueqi Liang; Kurt O. Konhauser (Geochimica et Cosmochimica Acta, 2026)

Dual-phase Co/CoFe nanoparticles anchored on N, F co-doped hollow carbon microcapsules as efficient bifunctional catalysts for aqueous/quasi-solid-state Zn-air batteries - Bin Cui; Yunfeng Zhu; Xingyue Fang; Renjing Du; Jiabao Bai; Mengran Li; Wanting Xiang; Wenxuan Xie; Yana Liu; Jiguang Zhang; Rui Shi; Jun Wang; et al. (Chemical Engineering Journal, 2026)

Complete upcycling of iron phosphate slag via ammonium sulfide: Synchronous recovery of phosphorus, Fe7S8/C catalyst, and elemental sulfur - Shaoxiang Yang; Fei Zhang; Yikun Li; Fang Wang; Jiayu Feng; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia (Chemical Engineering Journal, 2026)

Functionalizing 3D DNA crystals by replacing non-framework strands - Xinyu Feng; Li Xu; Yunhan Zhang; Shuheng Wei; Dongbao Yao; Huichao Chen; Yueye Wang; Yujing Wu; Hui Hou; Xiao Cui; Qian Meng; Yue Gu; et al. (Chemical Engineering Journal, 2026)

A LiF-rich and Ag-embedded dual-artificial solid-electrolyte interphase for stable Li metal anodes - Xun-Lu Li; Jian Bao; Wenyu Zhao; Chong-Yu Du; Rui-Jie Luo; Cui Ma; Jie Zeng; Xuan Xu; Zhe Qian; Zhe Mei; Xinyang Yue; Yong-Ning Zhou (Chemical Engineering Journal, 2026)

Impact of Vitamin E, Selenium, and Deferasirox on the Negative Effects of Experimental Coccidiosis - Yanbing Zhao; Juezhang Wang; Ruixin Zhu; Xiaoling Lv; Li Zhang; Ci Liu; Xiaozhen Cui; Rui Bai; Mingxue Zheng (Biological Trace Element Research, 2026)

High breeding potential for growth exists in normal, black, and golden shell lines of tetraploid Fujian oyster revealed through three generations of mass selection - Yuanxin Liang; Qi Li; Xianchao Bai; Geng Cheng; Jianmin Zhou; Rui Xu; Fanzhi Chu; Zhiyang Cui; Chengxun Xu; Wenshu Luo (Aquaculture, 2026)

Nutrient regimes shaping the diatom-dinoflagellate interdecadal succession in coastal temperate waters of China - Kan Chen; Keqiang Li; Guangshen Tan; Peiyi Gao; Guangmin Zhen; Rui Yang; Kunlong Yu; Xiansheng Zhang; Xiaoru Cui; Dongliang Lu; Shanqiao Chen; Eric P. Achterberg; et al. (Water Research, 2026)

Comprehensive evaluation on potentiality and key bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Ming-Teng Li; Yuan Sui (Process Safety and Environmental Protection, 2026)

Depleting SfCarE: Innovative strategies for enhancing chlorantraniliprole toxicity through mixing with carbaryl in Spodoptera frugiperda (Lepidoptera: Noctuidae) - Qinqin Wang; Lin Zhou; Li Wang; Xiangshuai Li; Pei Liang; Changhui Rui; Huizhu Yuan; Li Cui (Pesticide Biochemistry and Physiology, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Kinetic and spectroscopic studies on the inhibitory mechanisms of deoiled egg yolk hydrolysate against pancreatic lipase - Lin Zhang; Rui Cui; Wei Liu; Shasha Wang; Yifang Yan; Yi Wang; Xi Huang (Food Bioscience, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

Environmental stress and symbiotic shifts: The impact of perfluorooctanoic acid (PFOA) on soil microbe-plant networks - Zhan Chen; Jiajie Lou; Mengyao Yan; Rui Cui; Yicheng Jin; Mengwei Zhang; Rongshe Zhang; Shuduan Mao; Jun Chen; Liwei Sun; Tao Lu; Haifeng Qian (Environmental Pollution, 2026)

Design and preparation of PtY@ZnS-1 catalyst with applicable catalytic property for propane dehydrogenation - Rui Zhou; Hongjiang Li; Shenmin Li; Yingna Cui; Xinping Wang (Chemical Engineering Journal, 2026)

Robust oxygen vacancy surfaces induce chemical bonding interfaces of Bi2Sn2O7/Bi2MoO6 S-scheme heterojunction with asymmetric adsorption sites for efficient photocatalytic nitrogen fixation - Yongli Li; Xin Kong; Rui Bao; Liang Liu; Zhenhua Ge; Feng Liu; Hao Cui; Jianhong Yi (Chemical Engineering Journal, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

Corrigendum to “Anodic microbiota reassembly via cell-cell interactions confers oxygen resilience in microbial fuel cells” [Bioresour. Technol. 443 (2026) 133815] - Jingtong Dai; Xinyu Cao; Heng Xu; Can Wang; Likai Hao; Binbin Xie; Shun Li; Kelei Zhao; Lei Cui; Zhao Yin; Baoshi Yao; Tao Chen; et al. (Bioresource Technology, 2026)

Anodic microbiota reassembly via cell-cell interactions confers oxygen resilience in microbial fuel cells - Jingtong Dai; Xinyu Cao; Heng Xu; Can Wang; Likai Hao; Binbin Xie; Shun Li; Kelei Zhao; Lei Cui; Zhao Yin; Baoshi Yao; Tao Chen; et al. (Bioresource Technology, 2026)

Integrating CO2-EOR and Sequestration via Assisting Steam Huff and Puff in Offshore Heavy Oil Reservoirs with Bottom Water - Guodong Cui; Kaijun Yuan; Haiqing Cheng; Quanqi Dai; Xi Chen; Rui Wang; Zhe Hu; Zheng Niu (Journal of Marine Science and Engineering, 2026)
CO2-assisted steam huff and puff is an effective method to improve oil recovery and store CO2 in heavy oil reservoirs. However, few studies focused on complex geological formations, such as bottom water. The bottom water condition not only complicates the process of oil production and CO2 sequestration, but also makes migration and distribution of oil, water and CO2 unclear. In this paper, a numerical geological model of an offshore heavy oil reservoir with bottom water is established to analyze the influence of bottom water on injection and production parameters, oil recovery and CO2 storage capability under vertical and horizontal well layouts. The results show that the bottom water could maintain the formation pressure, but reduce the steam chamber radius and heavy oil utilization area, increase water production and decrease the oil–water ratio. CO2 could enhance oil recovery in the bottom water reservoir. Oil development indicators of the horizontal well are higher than the vertical well. Meanwhile, CO2-assisted steam huff and puff use in the bottom water reservoir can create a high-pressure and -temperature environment to make CO2 supercritical, as it has better CO2 storage capability and efficiency. The CO2 storage efficiency of the horizontal well is 63% larger than the vertical well. Thus, the horizontal well layout should be used as a priority if bottom water presents. Conducted analysis of bottom water formation sensitivity parameters shows that the advantageous formation conditions are high oil saturation, porosity of 0.2–0.4 and permeability of 2000–3000 mD. The influence degrees of each formation parameter were evaluated as well.

Effects of borneol on pharmacokinetics and tissue distribution of tetramethylpyrazine in transdermal patch - Lili Cui; Lichun Zha; Jiahua Mei; Rui Xue; Jie Wang; Ziwen Zhang; Yunshu Ma (Drug Delivery and Translational Research, 2026)

SEAF-Net: A Sustainable and Lightweight Attention-Enhanced Detection Network for Underwater Fish Species Recognition - Yu-Shan Han; Sheng-Lun Zhao; Chu Chen; Kangning Cui; Pingfan Hu; Rui-Feng Wang (Journal of Marine Science and Engineering, 2026)
This study presents SEAF-Net, a lightweight and efficient detection network designed for low-contrast and highly dynamic underwater environments. Built upon YOLOv11n, SEAF-Net introduces three complementary structural enhancements: (1) Omni-Dimensional Dynamic Convolution (ODConv) to improve adaptive modeling of multi-scale and directional texture variations; (2) SimA-SPPF, which embeds the SimAM attention mechanism into the SPPF module to enable neuron-level saliency reweighting and effective suppression of complex background interference; and (3) GhostC3k2 to reduce redundant computation while preserving sufficient representational capacity. Evaluated on a standardized 13-class underwater fish dataset under a unified training and evaluation protocol, SEAF-Net achieves 6.1 GFLOPs, 92.683% Precision, 88.459% Recall, 93.333% mAP50, 73.445% mAP, and a 90.522% F1-score. Compared with the YOLOv11n baseline, SEAF-Net improves F1-score and Recall by 0.510% and 0.575%, respectively, while reducing computational cost by approximately 6%, demonstrating a favorable accuracy–efficiency trade-off under lightweight constraints. Ablation results further confirm that SimA-SPPF plays a dominant role in background suppression, ODConv consistently enhances deformation and directional texture modeling, and GhostC3k2 effectively controls computational overhead without degrading detection accuracy. To assess deployment feasibility, additional test set evaluations were conducted under deployment-oriented conditions using resource-limited hardware, yielding an F1-score of 88.54%. This result confirms that the proposed model maintains stable detection performance and robustness beyond training and validation stages. Overall, SEAF-Net provides an effective balance of accuracy, efficiency, and robustness, offering practical support for low-carbon, scalable, and sustainable intelligent aquaculture monitoring and underwater ecological assessment in real-world environments.

YOLOv11-SDiseasedFishNet:Recognition of body surface symptoms of diseased fish based on automatic combination augmentation and multi-scale feature fusion - Zijian Wu; Jian Li; Rui Shi; Hongjing Dai; Zhibo Cui; Yue Wang; Hong Yu (Aquaculture, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Corrigendum to “Transcriptomic and biochemical analysis of the mechanism of sodium gluconate promoting the degradation of benzo[a]pyrene by Bacillus subtilis MSC4” [Journal of Environmental Sciences, Volume 152, June 2025, Pages 39-53] - Rui Chen; Tangbing Cui (Journal of Environmental Sciences, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Machine learning-enhanced electrochemical sensing platform for simultaneous detection of multiple antibiotics in food samples - Ting Zhang; Yuan Sun; Xin Zhang; Wenyu Cui; Rui Liu (Food Chemistry, 2026)

NCOA4-mediated ferritinophagy regulates AgNP-induced ferroptosis in lung cells - Rui Zhang; Haitao Yang; Menghao Guo; Shuyan Niu; Yu Ma; Xin Shen; Liqing Wu; Chenyu Liu; Mengjing Cui; Tianshu Wu; Yuying Xue (Food and Chemical Toxicology, 2026)

Bi single-atom decorated Cu/Cu2O heterostructure via spray pyrolysis for 100% selectivity in photocatalytic CO production - Danyang Ma; Xin Kong; Xin You; Liang Liu; Rui Bao; Hao Cui; Feng Liu; Jianhong Yi (Chemical Engineering Journal, 2026)

An enhanced GNSS/INS positioning method with position and attitude constraints in urban environments - Jianhui Cui; Xuan Han; Rufei Liu; Rui Tu; Yan Xiang; Shuangshuang Wu; Zeyu Li; Wenqian Zhou (GPS Solutions, 2026)

Vehicle-borne GNSS/INS integration performance in urban environments with KF-GINS, IGNAV, GINav, PSINS and OB-GINS - Wenqian Zhou; Jianhui Cui; Rui Tu; Rufei Liu; Zeyu Li; Xuan Han (Advances in Space Research, 2026)

A Hybrid CUBE-IForest Approach for Outlier Detection in Multibeam Bathymetry - Rui Han; Yukai Hong; Xibin Han; Yi Zhang; Shunming Hu; Yuan Huan; Xiaodong Cui; Xiaohu Li (Journal of Marine Science and Engineering, 2026)
With the rapid development and widespread application of multibeam echo-sounding systems, large-scale and high-resolution seafloor topography can be efficiently acquired, enabling precise mapping of seabed terrain. However, due to complex oceanographic conditions, instrumental noise, and acoustic interferences, the acquired multibeam data often contain outliers that deviate from the true seafloor surface. These outliers can distort the representation of seafloor topography, adversely affecting subsequent geological analysis and engineering applications. To address this issue, a hybrid outlier detection method combining CUBE filtering with the Isolation Forest (IForest) algorithm, termed CUBE-IForest, is proposed. The method first employs CUBE filtering to remove gross outliers based on local uncertainty estimation, followed by the application of IForest to identify subtle anomalies in the refined data, achieving hierarchical detection of outliers. Experimental results based on in situ multibeam bathymetric data from the northeastern Pacific demonstrate that compared with traditional filtering methods the CUBE-IForest approach significantly improves detection accuracy and reduces both false positive and false negative rates by approximately 30%, confirming its efficiency and reliability in seafloor mapping and analysis.

Spatiotemporal characteristics of RPL24 expression in the yak oviduct and its regulatory mechanism on epithelial cell proliferation via DDX3X/DDX5 - Yanhu Wang; Yangyang Pan; Rui Ma; Yuejiao Liao; Kangle Xian; Yan Cui; Sijiu Yu (Theriogenology, 2026)

Preparation of iron oxide/montmorillonite catalyst and its green remediation performance of pyrene-contaminated soil - Yun-rui Zhao; Kang Zhou; Xiao-xiao Qi; Hui Shi; Jihai Tang; Mifen Cui; Xu Qiao; Ming Xia (Journal of Water Process Engineering, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

The role of farm size in public goods provision: An agent-based model of habitat conservation in agricultural landscapes - Rong-Gang Cong; Jia-Rui Cui (Journal of Environmental Management, 2026)

Recent progress on Cu-based MOF electrocatalysts for CO2 reduction - Heng-fei Cui; Xiao-jing Liu; Cong Liu; Hao-wen Zhu; Ming-yang Liu; Rui-tang Guo (Fuel, 2026)

Photocatalytic carbon dots for food-borne hazards: Antimicrobial and degradation mechanisms and applications in the food industry - Dangfeng Wang; Wangqing Jiang; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Hongyan Guo; Fangchao Cui; Xuepeng Li; Tingting Li; Jianrong Li (Food Research International, 2026)

Metabolomics insights into the combined effects of boscalid and polystyrene microplastics on earthworms (Eisenia fetida): The critical role of pesticide dose and microplastics size - Zhiyuan Meng; Junting Shi; Rui Zhou; Yaqi Xiao; Xin Bao; Yaowen Cui; Sinuo Tian; Xiaojun Chen (Environmental Pollution, 2026)

A Janus-interface origami fog collector with spike arrays for efficient droplet transport - Ji QI; Congji ZHANG; Rui SONG; Muneerah Alomar; Tianze ZHANG; Yuxiang CHEN; Jiachang CUI; Shangzhen XIE; Zhiguang GUO (Chemical Engineering Journal, 2026)

Nitrogen sites induce homogeneous dispersion of iron species on biochar for enhanced hydrogen sulfide removal in a low-temperature anaerobic environment - Jiayu Feng; Fei Zhao; Huang Xiang; Fang Wang; Shuo Cui; Zibin Pan; Rui Cao; Ping Ning; Lijuan Jia (Bioresource Technology, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Vacuolar K⁺ efflux transporter TaTPK1-5D confers low-K⁺ tolerance of ‘Zhengmai 136’ through interaction with TaCIPK23-4D in bread wheat - Yingna Feng; Qianni Wei; Sisi Sun; Hongbing Zhang; Ting Zhou; Rui Cui; Wenxu Li; Yunqi Liu; Yingpeng Hua; Zhengfu Zhou (Theoretical and Applied Genetics, 2026)

The Role of Toll-like Receptor 3 Signaling in Cognitive Impairment Induced by Propofol Addiction - Jiahui Wu; Liyun Deng; Rui Gao; Ying Cui; Yidan Tang; Changliang Liu; Tao Zhu; Chan Chen (Molecular Neurobiology, 2026)

Mechanisms of Fish Intestinal Damage Under Environmental Stress: Insights From Carbonate Saline–Alkali Water Perspective - Jia Rui Cui; Qi Fang Lai; Yue‐Hong Li (Reviews in Aquaculture, 2026)
The intestinal tract is an important functional organ in fish, as it plays a key role in digestion and absorption, mucosal immunity, endocrine function, and metabolism. Therefore, damage to this organ greatly impacts fish health. This injury is usually associated with a poor aquaculture water environment, stressful conditions, and pathogen presence. In this review, in light of gut injury being a common pathology in aquaculture, we have summarized the current understanding of the intestinal damage of fish caused by carbonate water stress, and the mechanism of intestinal tissue damage caused by carbonate saline water stress, including the intestinal barrier function of fish and the role of various cells and molecules involved in the occurrence and development of diseases. Comparative data on carbonate stress responses across different teleost lineages (such as the Cyprinidae and Perciformes) have been integrated. The review also covers current methods for treating intestinal damage in fish, including dietary interventions, medications, and probiotics. Our findings highlight the need for more in‐depth research in this area to better understand the mechanisms underlying the occurrence of intestinal tissue damage in fish in carbonate‐based saline waters and to develop effective preventive and therapeutic strategies. Improved development of saline–alkaline waters and research into new treatments are essential for the sustainability of aquaculture and the health and productivity of farmed fish.

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Overexpression of the cold-repressed StWRKY70 enhances cold-induced sweetening resistance by coordinately attenuating starch-to-sugar conversion and increasing respiratory pathways - Rui Jiang; Chunyan Jiang; Xinyu Ni; Shuting Hu; Xiaoshuang Cui; Danting Li; Hui Sun; Tong Zhou; Jichun Wang; Dianqiu Lv; Xun Liu (Postharvest Biology and Technology, 2025)

Xylo-oligosaccharide utilization by Weissella kandleri YT103: Transcriptomic analysis and intestinal barrier protection - Xin-rui Zhang; Shuang-shuang Cui; Long-fen Yin; Gui-zhen Gong; Jian-xia Yang; Yang Chen; Yuan-ting Zhu (Food Research International, 2025)

Preparation and characterization of Ag@MOF-Amomum tsaoko essential oil/waterborne polyurethane composite films for strawberry preservation - Yuyue Qin; Hongda Yu; Haiyan Chen; Yongliang Zhuang; Qiuming Liu; Rui Cui; Cong Zhang; Charles Brennan; Yuanxiang Huang (Food Control, 2025)

Sustainable arsenic stabilization method for hazardous As Ca residues using magnetite tailings and carbide slag for scorodite formation: Implications for harmless treatment and waste reduction - Rui Su; Xuedi Wang; Miao Xu; Yuyin Ma; Yanjiao Gao; Xu Ma; Yubo Cui; Chunxue Bai; Shaofeng Wang (Chemical Engineering Journal, 2025)

Multiomics integration unveils rapeseed adaptative responses to potassium deprivation: a synergy of morpho-physiological, transcriptomic, and metabolic reprogramming - Rui Cui; Si-si Sun; Min-nan Pei; Ying Liu; Yu-shan Xiao; Ying-na Feng; Ting Zhou; Ying-peng Hua (Plant and Soil, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

TROAP aggravates chemoresistance of colorectal cancer cells via lipogenesis by PI3K/Akt pathway and histone acetylation - Ling-Ling Wang; Rui Zhang; Ning Li; Zheng-Guo Cui; Hua-Chuan Zheng (Functional & Integrative Genomics, 2025)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

Simulation on the propagation characteristics of TEM pseudo-wavefield - Jun-jie Xue; Ke-rui Fan; Xin Wu; Zhi-peng Qi; Wen-han Li; Jiang-wei Cui (Applied Geophysics, 2025)

Dynamics of multiple rogue waves for (3+1)-dimensional variable-coefficient potential Yu-Toda-Sasa-Fukuyama equation - Yi-Lin Tian; Wen-Yuan Li; Nong-Sen Li; Rui-Gang Zhang; Ji-Feng Cui (Wave Motion, 2025)

Hetero-protein systems: an effective strategy to improve the functional properties of protein - Yue-Yue Liu; Rui Cui; Teng-Gen Hu; Bing Li; Hong Wu (Trends in Food Science & Technology, 2025)

Investigation on unrecognized catalytic contributing role of chlorobenzene oxidation by iron ore in sintering process - Juexiu Li; Wenbo Xue; Huandan Cui; Xinrui Lei; Wenlong Zhou; Rui Zhao; Ziqiang Li; Chuanyi Fan; Zhongxian Song; Jinping Jia (Process Safety and Environmental Protection, 2025)

Prediction method of propeller tip vortex cavitation inception based on bubble dynamics models and change-point detection - Jia Duan; Rongwu Xu; Lilin Cui; Bin Ji; Rui Wu; Heng Liu; Chang Chen (Ocean Engineering, 2025)

Integrated assessment of chromium exposure risk from agricultural soils using chemical extraction, in vitro simulation, and mouse bioassay - Peng Xiao; Yi Zhou; Pengfei Wang; Rui Li; Shimao Xiong; Xiyan Jiang; Yunpeng Li; Yue Wu; Yuntao Yang; Xiaolin Cai; Naiyi Yin; Yanshan Cui (Journal of Hazardous Materials, 2025)

Na/N doped carbon dot nanozymes with enhanced peroxidase activity for antimicrobial food preservation - Dangfeng Wang; Yifan Hou; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Chemistry, 2025)

Residue behavior, processing factors and risk assessment of four new fungicides in grapes from field to processing - Kai Cui; Shuai Guan; Jingyun Liang; Rui Ni; Ruiyan Ding; Teng Li; Jian Wang; Junhua Liu; Liping Fang; Zhan Dong; Xiaohu Wu; Yongquan Zheng (Food Control, 2025)

Air pollution, drought, and their synergistic effects on cardiovascular disease risk in China: a nationwide study - Chaohao Ling; Rui Li; Qian Shen; Lulu Cui; Mangen Yang; Zhou Liu; Tianzhao Xu; Wenwen Sun; Shaofu He (Environmental Pollution, 2025)

Energy flexibility at multi-building scales: A review of the dominant factors and their uncertainties - George Dawes; Tuğçin Kirant-Mitić; Zixin Jiang; Jérôme Le Dréau; Hanmin Cai; Jiyuan Cui; Jordan Townsend; Adamantios Bampoulas; Rongling Li; Rui Amaral Lopes; Bing Dong (Energy and Buildings, 2025)

Dual-catalytic polymerization of high-performance PEDOT thermoelectric fabrics for self-powered sensing - Yifan Cui; Qin Chen; Wuwei Bao; Hao Yao; Zhenzhe Huang; Rui Ma; Miao Miao; Lizhi Sheng; Xinyang He (Chemical Engineering Journal, 2025)

Thermodynamic and kinetic improvement of MgH2 via the synergism of Al species and Nb-TiO2 - Mengran Li; Jialing Gu; Qinke Tang; Jiabao Bai; Bin Cui; Ruoyu Ma; Yunfeng Zhu; Rui Shi; Yao Zhang; Jiguang Zhang; Yana Liu; Jun Wang; et al. (Chemical Engineering Journal, 2025)

Ni/Al2O3 catalysts for the selective hydrogenation of 1,3–butadiene to butene: From theoretical research to experimental proving - Linxia Cui; Mingyuan Zhang; Xin Chen; Yuanyao Xie; Yang Jiang; Rui Gao; Haigang Hao (Chemical Engineering Journal, 2025)

Magnetic biochar-cored halophilic aerobic granules: Novel strategy for rapid formation and structural stability enhancement - Dong-Xu Zhou; You-Wei Cui; Ya-Nan Mi; Zhen-Ying Li; Rui-Chun Yang; Yuan Sui (Bioresource Technology, 2025)

Timosaponin B- II Enhances Osteogenic Differentiation of Human Periodontal Ligament Stem Cells via PI3K/AKT/GSK3β Signaling Pathway - Dai-Wei Yang; Xiao-Bin Cui; Rui Dong; Zhao-Yan Wu; Yu-Xing Zhang; Peng Yang; Jun Zhang (Stem Cell Reviews and Reports, 2025)

Effects of salt and cadmium stress on Suaeda salsa growth and soil quality - Ke Zhang; Rui Wang; Shuo Li; Qian Cui; Jiangbao Xia (Plant and Soil, 2025)

Cassiterite U–Pb ages from the Tin Islands, Indonesia, the southern end of the Southeast Asian tin province - Jie-Hua Yang; Rui-Zhong Hu; Mei-Fu Zhou; Bernd Lehmann; Jun-Hong Zhao; Jing-Hua Wu; Liang Liu; Wei Mao; Zheng-Teng Cui; Mega Fatimah Rosana (Mineralium Deposita, 2025)

Nine years of grazing and fertilization shape dynamics of soil phosphorus fractions in Karst pasture ecosystems - Wangfei Qin; Rui Dong; Xinyao Gu; Shaokun Hu; Song Cui; Xuechun Zhao; Jihui Chen; Yinglai Shi; Chao Chen; Yuan Li; Narasinha Shurpali; Mikko Järvinen; et al. (Agriculture, Ecosystems & Environment, 2025)

YOLOv11-OPNet: dual-modality framework for fishing vessel detection in complex long-range maritime scenarios - Jian Li; Hong Yu; Rui Shi; Zhibo Cui; Hongjing Dai; Zijian Wu; Yue Wang (Aquaculture International, 2025)

Extreme Phenotypic Variation Confounds Acanthocephalan Systematics: A Case Study of Longicollum pagrosomi and Pomphorhynchus zhoushanensis (Acanthocephala: Echinorhynchida) - Cui‐Hong Zhao; Hui‐Xia Chen; Matthew Thomas Wayland; Rui‐Jia Yang; Xiao‐Hong Gu; Liang Li (Zoologica Scripta, 2025)
The phylum Acanthocephala is a ubiquitous group of zooparasites, with major socio‐economic importance. The true diversity of the Acanthocephala is obscured by the phenomena of cryptic speciation and a large degree of intraspecific variation. In this study we describe an example of extreme phenotypic variation in neck morphology. The pomphorhynchid acanthocephalans, Longicollum pagrosomi and Pomphorhynchus zhoushanensis were originally differentiated on the basis of differences in neck morphology; P. zhoushanensis possesses a neck bulb whereas this structure is absent in L. pagrosomi . However, ASAP and phylogenetic analyses of the ITS, 12S, cox 1 and cox 2 sequence data, together with comparative mitogenomics, revealed that the two taxa are in fact conspecific. Therefore, the presence or absence of a neck bulb represents extreme phenotypic variation, and this character is not reliable for distinguishing the genera Pomphorhynchus and Longicollum. In the absence of other characters to discriminate the two genera, Longicollum is relegated to a junior synonym of Pomphorhynchus . A new combination Pomphorhynchus pagrosomi (Yamaguti, 1935) comb. nov. is proposed for L. pagrosomi Yamaguti, 1935 and P. zhoushanensis Li, Chen, Amin & Yang, 2017 is relegated to a junior synonym of P. pagrosomi .

Isolation, identification, and bioactivity evaluation of endophytic fungi from Ruta graveolens: insights into antimicrobial and antioxidant potential - Qianyun Hao; Wei Wang; Yanlin He; Chaoyong Cui; Jing Du; Rui Yang (Folia Microbiologica, 2025)

Harnessing synthetic microbial communities for sustainable agriculture: Enhancing soil health and crop yields - Yunhe Cui; Yue Tao; Yang Luo; Rui Sun; Siyue Han; Yang Yang; Zhongmin Dai; Ying Zhang (Critical Reviews in Environmental Science and Technology, 2025)

The internal and external reverse-reduction pathway involved in the degradation of free DNA bases during advanced oxidation processes - Shuangshuang Cheng; Rui Cui; Yuehong Sun; Yuxin Li; Yangjian Zhou; Zilong Song; Xin Yang (Water Research, 2025)

Nitrogen and phosphorus addition affected soil organic carbon storage and arbuscular mycorrhizal fungi contributions - Shengchao Ma; Rui Guo; Yue Wang; Yan Yan; Qianwen Chu; Nan Cui; Yifei Zhang; Lei Zhang; Li Jiang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; et al. (Journal of Environmental Management, 2025)

Electrospun Mn-doped ZIF-67 composite nanofibers with high water stability for efficient adsorption of antibiotics in aqueous systems - Xiaolin Yue; Can Cui; Shaolin Deng; Lan Wang; Ping Li; Anhong Li; Yizhong Zhang; Rui Hao; Wenyuan Tan (Journal of Environmental Chemical Engineering, 2025)

High internal phase emulsion system for curcumin delivery co-constructed by wheat gluten amyloid fibrils and Lycium barbarum polysaccharide - Ren Li; Rui Kang; Rumeng Li; Sai Cui; Huijuan Zhang (Food Research International, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Agar-based Pickering emulsion: A platform for enzymatic and chemoenzymatic synthesis - Cong Zhang; Rui Cui; Liang Qi; Minhua Zong; Canyu Zhang; Yufei Cao; Wenyong Lou (Chemical Engineering Journal, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

Low temperature efficient adsorption of toxic gas phosphine over CuCe co-doped nitrogen-rich biochar in an anaerobic environment - Ruoxu Liu; Min Shao; Junjie Ma; Fang Wang; Rui Cao; Zibin Pan; Ping Ning; Jiayu Feng; Shuo Cui; Lijuan Jia (Chemical Engineering Journal, 2025)

Differential responses in topsoil and subsoil: N2O, CO2, and CH4 dynamics under extreme rainfall - Mengdi Yang; Yufei Cui; Xiaomin Li; Ning Zhang; Shengli Guo; Rui Wang (CATENA, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Inhibition by dissolved organic matter of the degradation of purine compounds by the sulfate radical - Shuangshuang Cheng; Rui Cui; Jinpeng Yu; Yujie Zhao; Xin Yang (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

A salt-tolerant tetracycline degrading fungal strain of Candida palmioleophila: Characterization and degradation pathway - Zhen-Ying Li; You-Wei Cui; Hui-Juan Yan; Hui-Kai Liang; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Dissipation and metabolism of fluxapyroxad, oxathiapiprolin and penthiopyrad in grapes: A comprehensive risk assessment from field to raisins - Kai Cui; Liping Fang; Ruiyan Ding; Rui Ni; Jingyun Liang; Teng Li; Jian Wang; Junhua Liu; Shuai Guan; Zhan Dong; Xiaohu Wu; Yongquan Zheng (Food Chemistry, 2025)

Inactivation of Penicillium spp. in apple juice by pulsed light and the exploration of its mechanisms - Guolong Li; Saiqun Wang; Yu Li; Lu Cui; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang (Food Control, 2025)

Self-powered Ag2Se/SiO2/Si heterojunctions for ultrafast broadband high-sensitivity photodetection - Weipeng Shi; Rui Guo; Gailing Tian; Wenjing Zhang; Yi Chen; Wenyan Wang; Yonghua Wang; Danfeng Cui; Jinglong Wen; Dan Liu; Chenyang Xue (Chemical Engineering Journal, 2025)

Modulating the metal–support interaction of Pt/CeO2 catalysts for enhanced chemodynamic therapy for lung cancer thearanostics - Meijuan Ding; Tao Jia; Rui Xin; Guanghua Cui; Xiaoke Sun; Jialu Guo; Lili Feng; Yu Yang (Chemical Engineering Journal, 2025)

Transboundary intercellular communication mechanisms in the treatment of polyvinyl alcohol (PVA) wastewater by Geotrichum candidume enhanced activated sludge - Rui Zhang; Sixin Zhang; Chunrui Li; Bin Cui; Dandan Zhou (Water Research, 2025)

Resilience-based restoration sequence optimization of disrupted transportation networks: A novel matheuristic approach - Xinhao Cui; Bo Li; Siyue Zhang; Ziguang Ji; Shitao Wang; Rui Luo; Yi Ren; Yiyong Xiao (Transportation Research Part D: Transport and Environment, 2025)

One-billion-year-old eukaryotic algal fossil Arctacellularia from North China and its implications for the evolution of pre-Cryogenian filamentous multicellularity - Rui Huang; Guangjin Li; Jiayue Wang; Qing Tang; Mingyang Qiu; Qian Chen; Hanzhi Qu; Chengxi Wu; Wenfei Cui; Xianqin Yan; Chuanming Zhou; Xunlai Yuan; et al. (Precambrian Research, 2025)

Life-long impacts of nanoplastics to rice plant (Oryza sativa L.): Decreased grain yield with perturbed metallome and soil microbiome - Hongxin Xie; Xuejia Wang; Liwei Cui; Rui Chen; Rui Zhao; Yang Yu; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

High enrichment of heterotrophic nitrification-aerobic denitrification bacterial community achieved by shortening anoxic feeding duration in the sequencing batch reactor: feeding mode effect and mechanism - Yuan Sui; You-Wei Cui; Hui-Juan Yan; Rui-Chun Yang (Journal of Environmental Management, 2025)

Available medium and micronutrients in the soils of major citrus-producing areas in Southeast China - Zhangqian Xu; Yuzhou Zhou; Rui Liu; Haojie Cui; Jie Tan; Weijun Zhou; Kai Ouyang (Journal of Environmental Management, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Electroacupuncture may alleviate inflammatory pain by downregulating the expression of P2Y14 receptor in the primary somatosensory cortex - Shuai Hou; Cui-Yuan Chen; Rui-Zhu Zhou; Liu-Xuan He; Xiao-Xiao Zhao; Sha-Sha Chen; Sha Yang; Hai-Yan Yin; Shu-Guang Yu (Purinergic Signalling, 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Source analysis of soil selenium and evaluation of soil environmental quality and safety in the eastern area of Zichuan District, Shandong Province - Jia-Wen Cui; Li-Yuan Yang; Jie-Rui Dai; Xi-Qiang Zhao; Jia-Liang Li (Environmental Monitoring and Assessment, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

SETD2 regulates oocytes in vitro maturation through histone methylation and maternal mRNA degradation in yak - Hui Zhang; Yangyang Pan; Meng Wang; Jinglei Wang; Jiaxin Huang; Rui Ma; Shanshan Yang; Wenbin Ma; Sijiu Yu; Yan Cui (Theriogenology, 2025)

Tetracycline degradation by a mixed culture of halotolerant fungi-bacteria under static magnetic field: Mechanism and antibiotic resistance genes transfer - Zhen-Ying Li; You-Wei Cui; Hui-Kai Liang; Hui-Juan Yan; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

Addressing challenges and advancing solutions: Enhancing semi-coking wastewater treatment for a sustainable prospect - Tingting Cui; Chunhui Zhang; Bingxu Quan; Liwei Wang; Zhao Zhang; Peidong Su; Yuanhui Tang; Guifeng Zhao; Ping Qiao; Junqiang Guo; Rui Zhang (Journal of Environmental Management, 2025)

Cotreatment strategy for hazardous arsenic-calcium residue and siderite tailings via arsenic fixation as scorodite - Rui Su; Xinrong Su; Yanjiao Gao; Xu Ma; Xiaoming Zhao; Xiaoxia Ou; Yubo Cui; Jinru Lin; Yuanming Pan; Shaofeng Wang (Journal of Environmental Sciences, 2025)

Dispersion stability and thermal conductivity of modified ZnO/HFE-7100 nano-coolant - Yuxin Yang; Rixin Zhang; Rui Liang; Yike Gao; Chenyang Zhang; Junwei Cui; Shengshan Bi (International Journal of Refrigeration, 2025)

A new three-dimensional peak shear strength criterion of rock joints considering true-sheared asperities - Yingchun Li; Yue Cui; Yuzong Li; Rui Yong; Bo Li (International Journal of Rock Mechanics and Mining Sciences, 2025)

Responses of microbial community to different depths in volcanic soils of Nvshan Volcano - Jin Chen; Haining Wang; Ye Cui; Yiming Dai; Yueming Bao; Rui Qin; Qixiu Cheng; Xiaoyu Li (World Journal of Microbiology and Biotechnology, 2025)

Identification of alternative splicing transcripts of Dorsal from Procambarus clarkii and their roles in innate immunity - Ying Huang; Rui Shen; Li-Fan Cui; Qian Ren (Aquaculture, 2025)

Nitrogen addition and rhizosphere effects differentially shape prokaryotic and fungal communities in peanut–maize cropping systems - Yang Chen; Zejin Zhang; Yichao Rui; Carson Pearl; Sheng Lu; Fang Wang; Flemming Ekelund; Yanbin Hao; Xiaoyong Cui (Rhizosphere, 2025)

The combination of microplastics and glyphosate affects the microbiome of soil inhabitant Enchytraeus crypticus - Huihui Yang; Guogang Zheng; Guoyan Qin; Qi Zhang; Ziyao Zhang; Bingfeng Chen; Chaotang Lei; Meng Liu; Rui Cui; Liwei Sun; Shengjie Xia; W.J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2025)

Upcycling waste cartons into an efficient Fenton-like chainmail catalyst CoOx@C: Process, performance, and mechanism - Chen-Xuan Li; Wenhui Xu; Bai Li; Xiangyang Xu; Xian-Zhong Fu; Rui Deng; Feng Zhang; Yimin Sun; Kangping Cui (Journal of Environmental Chemical Engineering, 2025)

Transcriptomic and biochemical analysis of the mechanism of sodium gluconate promoting the degradation of benzo [a] pyrene by Bacillus subtilis MSC4 - Rui Chen; Tangbing Cui (Journal of Environmental Sciences, 2025)

Fluorescent molecularly imprinted hydrogel sensing strip based on nitrogen-doped carbon dots and inverse opal photonic crystals applying for effective detection for imidacloprid in fruits and vegetables - Mingfei Pan; Mengmeng Gao; Jingjing Cui; Rui Gao; Huilin Li; Jingming Sun; Wenjie Chen; Shuo Wang (Food Chemistry, 2025)

Hypoglycemic effects of Lactiplantibacillus plantarum B19 via promoting AMPK/PI3K/AKT signaling pathway - Mei-Jie Xiong; Rui Cui; Teng-Gen Hu; Hong Wu (Food Bioscience, 2025)

Preparation of chitosan/shellac nanoparticles-essential oil Pickering emulsion active film and its application in bread preservation - Jin-Ming Tan; Rui Cui; Teng-Gen Hu; Xiao-Xi Li; Hong Wu (Food Packaging and Shelf Life, 2025)

Volcanic CO2 emissions from subduction of the tropical Paleo-Tethyan Ocean contributed to the early Permian deglacial warming - Wei Feng; Jianghai Yang; Peter A. Cawood; Rui Ma; Yinsheng Zhou; Ying Cui (Earth and Planetary Science Letters, 2025)

Synergistic optimization of bulk defects and back contact in Cu2ZnSn(S,Se)4 solar cells via inducing the heavy-rare-earth erbium ions - Lulu Bai; Yanchun Yang; Guonan Cui; Rui Wang; Zhihui Gong; Shuyu Li; Yongjun Cao; Chengjun Zhu (Chemical Engineering Journal, 2025)

Heavy-Duty Diesel Trucks on Highways in Beijing-Tianjin-Hebei: Constant Challenge in Pollution Control - Yingying Han; Chang Wang; Yixue Zhu; Rui Wu; Yifeng Xue; Xiang Zhang; Weiwei Wang; Yangyang Cui; Jinxiu Han; Zongbo Shi; Xiuyan Wang; Taosheng Jin (Water, Air, & Soil Pollution, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

The Influence of Vickers Hardness and Brittleness on Particle Size Distribution During Ball Milling: A Multifractal Approach - Sheng Zhang; Yichao Rui; Zilong Zhou; Xin Cai; Hongzhi Cui (Rock Mechanics and Rock Engineering, 2025)

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Global trends in staphylococcus aureus-related lower respiratory infections from 1990 to 2021: findings from the 2021 global burden of disease report - Hong Chen; Shuang Song; Rui Cui; Yong-Wang Feng; Peng Ge (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Integrative transcriptomic and physiological analyses uncover mechanisms by which arbuscular mycorrhizal fungi mitigate salt stress in sugar beet - Zeyuan Cui; Xiaodong Li; Pingan Han; Rui Chen; Yinzhuang Dong; Gui Geng; Lihua Yu; Jiahui Liu; Yao Xu; Yuguang Wang (Mycorrhiza, 2025)

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

Genome-based taxonomy of the family Haloarculaceae, proposal of Natronomonadaceae fam. nov., and description of four novel halophilic archaea from two saline lakes and a marine solar saltern - Ling-Rui Zhu; Ya-Ling Mao; Yao Hu; Ya-Ping Sun; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

Flood complexity and rising exposure risk in High Mountain Asia under climate change - Yuanyuan Bai; Dongfeng Li; Sonam Wangchuk; Albert Kettner; Yi Zhao; Rui Deng; Yong Liu; Cunde Xiao; Jinren Ni; Peng Cui (Science Bulletin, 2025)

Recovery of volatile ethanol gas via microalgal-bacterial consortium: Ethanol-to-acetate conversion pathway boosts lipid production - Liu-Xu Jiang; You-Wei Cui; Ya-Nan Mi; Dong-Xu Zhou; Ming-Teng Li; Rui-Chun Yang (Journal of Environmental Management, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Inactivation activity and mechanism of natural antimicrobial agents against Alicyclobacillus spp. in apple juice - Rui Cai; Linlin Gao; Yuxiang Zhang; Lu Cui; Yahong Yuan; Zhouli Wang; Tianli Yue (Food Control, 2025)

Application of a new packaging material in the postharvest quality and spoilage microorganisms bacteria of morels - Kai Jiang; Yiwei Huang; Rui Cui; Yuyue Qin; Thanapop Soteyome; Margaret Brennan; Charles Brennan (Food Control, 2025)

Microstructure evolution of SOFC pure Ni anode with carbon deposition under polarization - Dongxu Cui; Ryo Kato; Yosuke Komatsu; Anna Sciazko; Bin Wang; Yue Xu; Shiliang Wu; Dengyu Chen; Rui Xiao; Naoki Shikazono (Chemical Engineering Journal, 2025)

Nitrogen enhances drought tolerance of maize during the jointing stage by increasing the proportion of deep nodal roots and reducing the biosynthesis of lignin in root system - Dasheng Zheng; Yujie Cun; Bingxiao Du; Zhifeng Cui; Yuanhua Ma; Yulan Ye; Yue Zhang; Rui Wang (Plant and Soil, 2025)

Experimental and Numerical Investigation on Mechanical Properties of Large-Diameter Metallurgically Clad Pipes - Feng Wang; Yanan Gao; Zhiguo Hu; Shuo Yang; Zhenying Cui; Rui Fu; Lin Yuan (Journal of Marine Science and Engineering, 2025)
Bimetallic-clad pipes demonstrate exceptional advantages in transporting corrosive oil and gas through the combination of the load-carrying capacity of the base material and the anti-corrosive function of the thin layer of corrosion-resistant alloy. This study investigates the mechanical properties of 24-inch X65 + Alloy625 metallurgically clad pipes through experimental tests and finite element analysis. Uniaxial tensile testing with digital image correlation reveals uniform deformation between the base and clad layers until interfacial failure initiates at an average strain threshold of 34.17%. Microstructural characterization shows continuous metallurgical bonding, with the X65 layer exhibiting polygonal ferrite and bainitic phases, contrasting with the austenitic equiaxed grain structure of Alloy625. In terms of numerical modeling, finite element analyses that consider both initial geometric imperfections and manufacturing-induced residual stresses are performed to evaluate the bending response of the clad pipe. The effect of initial ovality and residual stresses on its bending capacity is also studied.

Based on NRCS and the Doppler centroid anomaly in SAR images to retrieve the nearshore bathymetry - Rui Qi; Jiamin Lin; Jian Wang; Xiaonan Yao; Xiaoqing Wang; Xinzhe Yuan; Lei Cui; Peiqing Yang; Xingyi Su (International Journal of Remote Sensing, 2025)

Millennial-scale surface hydrological variability in the tropical eastern Indian Ocean linked to Northern Hemisphere high latitudes - Rui Cui; Peng Zhang; Jian Xu; Ann Holbourn; Wolfgang Kuhnt (Frontiers in Marine Science, 2025)
Surface hydrology in the tropical eastern Indian Ocean significantly impacts low-latitude climate processes including the Indonesian-Australian Monsoon and the Indian Ocean Dipole. Deciphering the evolution of surface hydrology and driving mechanisms is thus important to better understand low-latitude and global climate change. Here, we present ~206 yr-resolved temperature and salinity records of surface waters spanning the past ~31 kyr, based on δ 18 O and Mg/Ca ratio of Globigerinoides ruber from Core SO18567 retrieved offshore northwestern Australia in the tropical eastern Indian Ocean. By integrating new records with published paleo-oceanographic and -climatological records, we found that increasing sea surface temperature and decreasing salinity in the tropical eastern Indian Ocean during the Heinrich stadial 1 and the Younger Dryas could be attributed to collapse of the Atlantic Meridional Overturning Circulation (AMOC). Melting of Northern Hemisphere ice sheets would have led to a southward shift of the Intertropical Convergence Zone (ITCZ) and reduced transport of warm surface waters from the low latitudes to the Northern Hemisphere high latitudes. In addition, our results indicate that the onset of the last deglacial warming in low latitudes was linked to weakening of the Hadley circulation and AMOC due to warming of Northern Hemisphere high latitudes, rather than raised global atmospheric CO 2 concentration.

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation” [Food Research International 203 (2025) 115792] - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

Robust lubricity and multifunctional water-based lubrication system induced by ionic liquids with its interfacial self-assembly behavior and unique hydration structure - Mengyao Liu; Yingying Yao; Bingyu Tian; Kun Cui; Ping Wen; Rui Dong; Mingjin Fan (Chemical Engineering Journal, 2025)

Pathogenic characterization and drug resistance of neonatal sepsis in China: a systematic review and meta-analysis - Ruixue Wu; Xiaoyu Cui; Rui Pan; Na Li; Ying Zhang; Jianbo Shu; Yang Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Halobellus marinus sp. nov., Halobellus ordinarius sp. nov., Halobaculum rarum sp. nov., and Halorarum halobium sp. nov., halophilic archaea isolated from marine solar salt and a saline lake - Ling-Rui Zhu; Chidiebele Nwankwo; Jing Hou; Heng-Lin Cui (Extremophiles, 2025)

Nuclear receptor coactive 4-mediated ferritinophagy: a key role of heavy metals toxicity - Wan-Xue Xu; Xue Wen; Yi-Tong Fu; Jie Yang; Han Cui; Rui-Feng Fan (Archives of Toxicology, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Structure, sources, functional mechanisms, and applications of bioactive glycopeptides in food: A comprehensive review - Dangfeng Wang; Benyou Zhang; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Trends in Food Science & Technology, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Fruit wines classification enabled by combing machine learning with comprehensive volatiles profiles of GC-TOF/MS and GC-IMS - Changlin Zhou; Yashu Yu; Jingya Ai; Chuan Song; Zhiyong Cui; Quanlong Zhou; Shilong Zhao; Rui Huang; Zonghua Ao; Bowen Peng; Panpan Chen; Xiaoxiao Feng; et al. (Food Research International, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Decoding the end-Devonian Hangenberg oceanic anoxia event: Insights from ironstones in South China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Ying Cui; Rui-Zhong Hu; Zerui Ray Liu; Xiyao Li (Earth and Planetary Science Letters, 2025)

Recombinant Human Nerve Growth Factor Integrated Hyaluronic Acid Hydrogel Microneedles for Corneal Nerve Repairing - Ziqing Feng; Rui Liu; Ruoyan Wei; Yunzhe Wang; Tianze Cui; Chang Liu; Xiaojun Hu; Chi Zhang; Bin Kong; Meiyan Li; Xingtao Zhou (Chemical Engineering Journal, 2025)

Damage Analysis of High-Frequency Disturbance in Sandstone Creep Process Based on NMR Technology - Jie Chen; Ziyang Chen; Xiaokang Pan; Yi Cui; Yicao Rui; Jinlai Zhao; Lei Gou (Rock Mechanics and Rock Engineering, 2025)

Land use patterns change N and P cycling bacterial diversity in an acidic karst soil - Zhou Li; Wangfei Qin; Yongliang You; Jihui Chen; Xuechun Zhao; Rui Dong; Xinyao Gu; Song Cui; Chao Chen; Erinne Stirling; Ran Xue (Agriculture, Ecosystems & Environment, 2025)

STYX Interacts with FBXW7 to Promote AML Proliferation via Inhibiting the Ubiquitination of CCNE1 - Rui Yang; Jing Ning; Hainan Wang; Hui Ma; Lijuan Cui (Cell Biochemistry and Biophysics, 2025)

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Early-Middle Holocene climate change and its impact on the succession of Neolithic cultures in southern Hangzhou Bay - Jing Lu; Haiwei Zhang; Rui Zhang; Jiahui Cui; Yanyan Bao; Xiaowen Niu; Yanjun Cai; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A data-driven framework to identify influencing factors for soil heavy metal contaminations using random forest and bivariate local Moran's I: A case study - Rui Zhou; Jian Chen; Shiwen Cui; Lu Li; Jiangbo Qian; Hang Zhao; Guoxin Huang (Journal of Environmental Management, 2025)

Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

Development of heat tolerance resulted from adaptation of Salmonella Enteritidis to sublethal concentration of sodium hypochlorite - Yuan Liang; Mengjun Hu; Rui Dong; Shoukui He; Yan Cui; Jinzeng Yang; Xiangyu Deng; Xianming Shi (Food Bioscience, 2025)

Enhancement of antibacterial activity of cinnamaldehyde against Bacillus cereus by nanoemulsion and its application in milk - Rui Cui; Fu-Yu Liu; Hong Wu (Food Bioscience, 2025)

Improving the bactericidal activity of carvacrol against Bacillus cereus by the formation of sodium casein-stabilized nanoemulsion and its application in milk preservation - Jun Li; Fu-Yu Liu; Bao-Lin He; Rui Cui; Hong Wu (Food Hydrocolloids, 2025)

RNA-Seq-based WGCNA reveals the physiological and molecular responses of poplar leaves to NaHCO3 stress - Song Jiaqi; Wang Jiechen; Qin Rui; Ji Guangxin; Cui Congcong; Sun Nan; Qi Siyue; Ding Changjun; Zhang Huihui (Trees, 2025)

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

The reverse-reduction effect of dissolved organic matter on the degradation of micropollutants induced by halogen radicals (Cl2•- and Br2•-) - Shuangshuang Cheng; Rui Cui; Yangjian Zhou; Yu Lei; Ni Wang; Yanheng Pan; Xin Yang (Water Research, 2025)

Bioenhanced remediation of dibutyl phthalate contaminated black soil by immobilized biochar microbiota - Yue Tao; Yao Wang; Yunhe Cui; Rui Sun; Bo Zhang; Jianhua Qu; Hongguang Cai; Ying Zhang (Journal of Environmental Management, 2025)

DFT study the influence of active site structure on the electrocatalytic nitrogen reduction reaction - Ke Shi; Linxia Cui; Mingyuan Zhang; Yang Jiang; Rui Gao; Haigang Hao (Fuel, 2025)

Aged garlic oligosaccharides modulate host metabolism and gut microbiota to alleviate high-fat and high-cholesterol diet-induced atherosclerosis in ApoE−/− mice - Xiaomin Wang; Jianglu Cui; Ziyao Gu; Lili Guo; Rui Liu; Yu Guo; Nan Qin; Yukun Yang (Food Chemistry, 2025)

Screening and characterization of an antifreeze peptide from sea cucumber intestinal protein hydrolysates - Zhe Xu; ShengAo Cao; Na Cui; Rui Zhang; Zijin Qin; Hanxiong Liu; Jianping Wu; Ming Du; Zhijian Tan; Tingting Li (Food Chemistry, 2025)

Effects of chitosan/eugenol-loaded IRMOF-3 nanoparticles composite films on reactive oxygen species metabolism and microbial community dynamics in postharvest strawberries - Yuyue Qin; Hongda Yu; Kejun Chen; Rui Cui; Jianxin Cao; Zhengxuan Wang; Zhi-Hong Zhang; Thanapop Soteyome (Food Bioscience, 2025)

Potential of probiotic-fermented Flos sophorae as a functional food: Enhanced anti-hyperuricemic activity and modulation of volatile components - Rui Cui; Cong Zhang; Zhen-Hui Pan; Teng-Gen Hu; Hong Wu (Food Bioscience, 2025)

Improved viability of probiotics by co-encapsulation of wheat germ oil under storage and gastrointestinal conditions: Effects of drying methods and wall composition - Bao-Lin He; Rui Cui; Teng-Gen Hu; Hong Wu (Food Hydrocolloids, 2025)

Identification and characterization of 16 tripartite motif-containing proteins from Takifugu obscurus - Li-Fan Cui; Rui Shen; Xiao-Rui Song; Yan Shi; Zhe Zhao; Ying Huang (Fish & Shellfish Immunology, 2025)

Design method of simplified dynamic test model for high-rise building with underground structures considering nonlinear behavior similarity - Rui Wang; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Yao-Zhong Cui; Han Zhang; Jia-Long Li (Engineering Structures, 2025)

Synergistic improvements of properties of cellulose acetate based curcumin@TiO2 nanofibers via triaxial electrospinning - Wenbin Deng; Yu Liu; Cui He; Xiaozhou Xiong; Rui Zhang; Tingfei Yan; Shuichao Shi; Deng-Guang Yu; Haisong Yang (Chemical Engineering Journal, 2025)

Flower-structured CoP@MoS2-x S-scheme heterojunction photocatalysts for enhanced hydrogen evolution and selective biomass oxidation - Jia Zhang; Jiliang Ma; Rui Cui; Weikang Ling; Min Hong; Runcang Sun (Chemical Engineering Journal, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

From biomass to power: High-performance reactor design for coking-resistant operation - Bin Wang; Tong Wang; Dongxu Cui; Tao Li; Rui Xiao (Bioresource Technology, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Portable paper-based microfluidic devices with Cu1-xAgxS NPs modification for multiplex intelligent visualized detection of adrenaline and glucose simultaneously - Huan Wang; Lihua Dong; Gina Ma; Shuang Qiu; Guiye Shan; Lijia Zhao; Yu Sun; Anni Cui; Rui Zhang; Xiaojie Liu (Analytica Chimica Acta, 2025)

Simulating the multi-media fate of perfluorooctane sulfonate (PFOS) and its precursors in the Bohai coastal region of China - Guoxiang Han; Shuai Song; Di Du; Haotian Cui; Yonglong Lu; Rui Wang (Science of The Total Environment, 2024)

Machine learning models reveal how polycyclic aromatic hydrocarbons influence environmental bacterial communities - Mingyu Gao; Guogang Zheng; Chaotang Lei; Rui Cui; Jun Chen; Jiajie Lou; Liwei Sun; Tao Lu; Haifeng Qian (Science of The Total Environment, 2024)

Investigation of the interactions and influencing factors of the Water-Land-Energy-Carbon system in the Yellow River Basin - Jiaxin Li; Xiaopeng Liu; Li Wei; Xinyan Li; Haiyan Gao; Rui Chen; Yifeng Cui (Science of The Total Environment, 2024)

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

Emission estimation and health risk evaluation of aquaculture drugs commonly used in China - Rui Wang; Yonglong Lu; Shuai Song; Shengjie Yang; Haotian Cui (Science of The Total Environment, 2024)

Spatial patterns, source apportionment, and risk assessment of polychlorinated biphenyls (PCBs) in the surface sediments of eastern China lakes along a latitudinal gradient: Insights guided by full-congener analysis - Jing Dong; Xingru Zhao; Ran Dai; Rui Guo; Chengyou Liu; Xiaoai Cui; Yaqing Liu; Hui Wang; Binghui Zheng (Journal of Hazardous Materials, 2024)

A free radical interlocking co-deposition strategy based on the oxidative pyrolysis mechanism of polyethylene terephthalate to achieve green energy recovery - Weiwen Gu; Tianyi Ma; Xinyu Cui; Xiaoyu Gu; Jun Sun; Jinping Xiong; Rui Wang; Sheng Zhang (Journal of Hazardous Materials, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

1T/2H-MoS2/CdS heterojunction for the co-production of lactic acid photoreforming to hydrogen and value-added chemicals - Ermiao Liang; Xue Liu; Zheng Yang; Jifang Zhang; Yabo Qi; Rui Teng; Wenbo Cui; Mingcong Xu; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Journal of Environmental Chemical Engineering, 2024)

Occurrence and distribution of phytic acid and its degradation products in soybeans in China: Analytical challenges - Jiayue Chen; Zhenjun Liu; Xinru Cui; Rui Yang; Xinru Guo; Guiqiao Liu; Chunmei Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2024)

The effect of LuxR solo EvgA on the spoilage potential of Pseudomonas fluorescens - Dangfeng Wang; Benyou Zhang; Yunting Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Fangchao Cui; Tingting Li; Jianrong Li (Food Bioscience, 2024)

Phosvitin phosphopeptides and peptides-calcium chelate promote calcium deposition in a three-cell co-culture system by modulating the OPG/RANKL/RANK signaling pathway - Jiaojiao Chen; Songming Li; Mahmoud Abou-Elsoud; Wei Liu; Rui Cui; Zuyue Li; Dewei Shu; Zhaoxia Cai; Xi Huang (Food Bioscience, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

MoS2 coupled with ball milling co-modified sludge biochar to efficiently activate peroxymonosulfate for neonicotinoids degradation: Dominant roles of SO4•-, 1O2 and surface-bound radicals - Yifan Liu; Yongfei Ma; Zhikang Deng; Ping Li; Song Cui; Chenyu Zeng; Rui Mu; Yusheng Zhou; Xuebin Qi; Zulin Zhang (Environmental Research, 2024)

Vitrification cryo-foil method for shoot tip cryopreservation and virus eradication in apple - Min-Rui Wang; Jun-Hua Bao; Xiao-Yan Ma; Zi-Han Yan; Zhen-Hua Cui; Li-Ying Zhu; Dong Zhang; Qiao-Chun Wang (Cryobiology, 2024)

Multifunctional flexible self-supporting film electrode for wearable energy-storage sensing system - Guoju Zhang; Zijian Gao; Chongyang Zhu; Fuhan Cui; Zhenjing Jiang; Rui Pan; Jiaxin Shen; Lin Zhu; Bowen Jiang; Litao Sun; Kuibo Yin (Chemical Engineering Journal, 2024)

Lipid nanoparticle-mediated base-editing of the Hao1 gene achieves sustainable primary hyperoxaluria type 1 therapy in rats - Dexin Zhang; Rui Zheng; Zhoutong Chen; Liren Wang; Xi Chen; Lei Yang; Yanan Huo; Shuming Yin; Dan Zhang; Jiaxin Huang; Xingang Cui; Dali Li; et al. (Science China Life Sciences, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Genome‑based classification of the family Natrialbaceae and description of four novel halophilic archaea from three saline lakes and a saline-alkaline land - Xin-Yue Dong; Ya-Ling Mao; Qing-Ke Zhang; Ling-Rui Zhu; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Tracking the impact of typhoons on maize growth and recovery using Sentinel-1 and Sentinel-2 data: A case study of Northeast China - Yongling Mu; Shengbo Chen; Yijing Cao; Bingxue Zhu; Anzhen Li; Liang Cui; Rui Dai; Qinghong Zeng (Agricultural and Forest Meteorology, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Response of soil gross nitrogen mineralization to fertilization practices in China's uplands - Jun Wang; Yinghua Duan; Guanmo Li; Lu Zhang; Dejin Li; Kailou Liu; Xi'an Cui; Boku Zhou; Hongjun Gao; Xiaori Han; Junyong Ma; Shutang Liu; et al. (Journal of Cleaner Production, 2024)

Cyanide content, nutrient composition, physicochemical properties and sensory quality of flaxseed oil bodies prepared from flaxseeds (Linum usitatissimum L.) treated with different heat treatment methods - Rui Zheng; Hui-Lin Liu; Nan-Nan Cui; Jun-Zhuo Zhou; Xin Sun; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2024)

Mg and Fe co-loaded biochar prepared by microwave-synergized K2FeO4 of marine biomass for efficient CO2 capture: Performance assessment and mechanism exploration - Juan Luo; Kai Sun; Shichang Sun; Rui Ma; Chongwei Cui; Han Cui (Chemical Engineering Journal, 2024)

Six element high-entropy Prussian blue analogue cathode enabling high cycle stability for sodium-ion batteries - Zhe Qian; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Xuan Xu; Zhe Mei; Zi-Ting Zhou; Zheng-Wen Fu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

Multifunctional visible light photocatalytic carbon dots synergize with reactive oxygen species for anti-quorum sensing and anti-bacteria for salmon preservation - Fangchao Cui; Xin Wang; Dangfeng Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Yilin Lu; Xuepeng Li; Tingting Li; et al. (Chemical Engineering Journal, 2024)

Mechanism of o-cresol polymerization and its carbon recovery from aqueous solution by a cathode/Fe2+/H2O2 process - Sui-Qin Yang; Yu-Hong Cui; Wei-Jun Xue; Zheng-Qian Liu; Rui Hu; Xiao-Qian Ye (Chemical Engineering Journal, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Residual plastic film decreases crop yield and water use efficiency through direct negative effects on soil physicochemical properties and root growth - Xiaobo Gu; Rui Yin; Wenjing Cai; Pengpeng Chen; Kui Cui; Yadan Du; Yuannong Li; Huanjie Cai (Science of The Total Environment, 2024)

Efficient degradation of Rhodamine B by visible-light-driven biomimetic Fe(III) complex/peroxymonosulfate system: The key role of FeV=O - Chen-Xuan Li; Rui Wang; Wen Sun; Kangping Cui; Xian-Zhong Fu; Minshu Cui; Yihan Chen; Zhi Guo; Yingying Liu (Journal of Environmental Chemical Engineering, 2024)

Self-assembly metal phenolic network coating improves the controlled release and bacteriostatic properties of Litsea cubeba essential oil-loaded ε-polylysine-pectin nanoparticles - Pengcheng Zhao; Rui Cui; Weiwei Li; Fang Zhang; Xianghong Meng; Bingjie Liu (Food Bioscience, 2024)

Advancing the treatment of low carbon-to-nitrogen ratio municipal wastewater using a novel microaerobic sludge bed approach: Insights into enhanced performance and functional microbial community - Wenbo Li; Xiao Zhang; Bowei Zhao; Ying Cui; Philip Antwi; Rui Li; Aijuan Zhou; Jinping Li; Xiuping Yue (Environmental Research, 2024)

Spatial distribution and enrichment characteristics of selenium in paddy soil and rice around the Dongting Lake - Rui Liu; Weijun Zhou; De Yu; Guiduo Shang; Yuzhou Zhou; Zhangqian Xu; Dou Tang; Haojie Cui; Chaolin Liao (Environmental Pollution, 2024)

Tracking the Molecular-Scale Mechanistic Pathway of Trapping-Bonding CTAB/Fe3O4-AS for High-Performance Cr(VI) Adsorption - Binqiao Ren; Yu Jin; Xiaoxiao Song; Luyang Zhao; Xue Han; Yuying Zhang; Chongwei Cui; Rui Liu; Han Cui (Chemical Engineering Journal, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Investigating thermal exposure during daily walking through a human-scale approach: An analysis of a hot summer in Wuhan - Jiwei Xu; Xinkun Xu; Zimeng Wang; Huiting Chen; Qiran Ren; He Huang; Yao Cui; Rui An; Yaolin Liu (Building and Environment, 2024)

Arbuscular Mycorrhizal Fungi Enhance Tolerance to Drought Stress by Altering the Physiological and Biochemical Characteristics of Sugar Beet - Zeyuan Cui; Rui Chen; Tai Li; Bingchen Zou; Gui Geng; Yao Xu; Piergiorgio Stevanato; Lihua Yu; Vadim N. Nurminsky; Jiahui Liu; Yuguang Wang (Sugar Tech, 2024)

Plastic particles and fluorescent brightener co-modify Chlorella pyrenoidosa photosynthesis and a machine learning approach predict algae growth - Yaodan Dai; Zhi Guo; Xingpan Guo; Rui Deng; Lele Li; Ting Fan; Kangping Cui; Tao Pan (Journal of Hazardous Materials, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Biotemplate synthesis of graphitic carbon-doped ZnO tube bundles rich in oxygen vacancies for dual-sensing of NO2/H2S at different temperatures - Zhao-Qi Cui; Rui Gao; Guo-Li Chen; Shi-Kai Shen; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Farrerol Alleviates Cerebral Ischemia–Reperfusion Injury by Promoting Neuronal Survival and Reducing Neuroinflammation - Rui Zhao; Xin Zhou; Zhiyuan Zhao; Wenhao Liu; Mengfei Lv; Zhaolong Zhang; Changxin Wang; Tianli Li; Zixiong Yang; Qi Wan; Rui Xu; Yu Cui (Molecular Neurobiology, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Tuning electronic environment of B sites in boron carbonitride nanoribbon boosts catalytic activity of reducing N2 to NH3 - Kai Zhang; Rui Zhang; Yuxin Cui; Jiayin Shang; Xueling Wei; Sumin Wang; Siqin Jia; Ke Qin; Haiyan Zhang; Hongyan Wang; Taotao Ai; Qiguan Wang (Fuel, 2024)

Development of machine learning-based shelf-life prediction models for multiple marine fish species and construction of a real-time prediction platform - Fangchao Cui; Shiwei Zheng; Dangfeng Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Xuepeng Li; Tingting Li; Jianrong Li (Food Chemistry, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Removal of artificial sweeteners in wastewater treatment plants and their degradation during sewage sludge composting with micro- and nano-sized kaolin - Jishao Jiang; Rui Hou; Huilin Cui; Zhuyu Tang; Yousif Abdelrahman Yousif Abdellah; Caspar C.C. Chater; Ke Cheng; Fuqiang Yu; Dong Liu (Bioresource Technology, 2024)

Identification of key genes involved in lignin and flavonoid accumulation during Tilia tuan seed maturation - Lei Liu; Cui Long; Xuri Hao; Rui Zhang; Chenqi Li; Yuepeng Song (Plant Cell Reports, 2024)

Materials for sustainable metallic iron-based water filters: a review - Minhui Xiao; Rui Hu; Willis Gwenzi; Ran Tao; Xuesong Cui; Huichen Yang; Chicgoua Noubactep (Environmental Chemistry Letters, 2024)
Water pollution is calling for a sustainable remediation method such as the use of metallic iron (Fe 0 ) to reduce and filter some pollutants, yet the reactivity and hydraulic conductivity of iron filters decline over time under field conditions. Here we review iron filters with focus on metallic corrosion in porous media, flaws in designing iron filters, next-generation filters and perspectives such as safe drinking water supply, iron for anaemia control and coping with a reactive material. We argue that assumptions sustaining the design of current Fe 0 filters are not valid because proposed solutions address the issues of declining iron reactivity and hydraulic conductivity separately. Alternatively, a recent approach suggest that each individual Fe 0 atom corroding within a filter contributes to both reactivity and permeability loss. This approach applies well to alternative iron materials such as bimetallics, composites, hybrid aggregates, e.g. Fe 0 /sand, and nano-Fe 0 . Characterizing the intrinsic reactivity of individual Fe 0 materials is a prerequisite to designing sustainable filters. Indeed, Fe 0 ratio, Fe 0 type, Fe 0 shape, initial porosity, e.g. pore size and pore size distribution, and nature and size of admixing aggregates, e.g. pumice, pyrite and sand, are interrelated parameters which all influence the generation and accumulation of iron corrosion products. Fe 0 should be characterized in long-term experiments, e.g. 12 months or longer, for Fe dissolution, H 2 generation and removal of contaminants in three media, i.e., tap water, spring water and saline water, to allow reactivity comparison and designing field-scale filters.

Genome-based classification of the family Haloferacaceae and description of five novel species of Halobaculum - Shun Tan; Ling-Rui Zhu; Qing-Ke Zhang; Xin-Yue Dong; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Repetitive Transcranial Magnetic Stimulation-Mediated Neuroprotection in the 5xFAD Mouse Model of Alzheimer’s Disease Through GABRG2 and SNAP25 Modulation - Jinyang Wang; Chenming Zhou; Zhimin Huang; Xiaoming Ji; Rui Cui; Yunxiao Kang; Guoliang Zhang; Yu Wang; Tianyun Zhang (Molecular Neurobiology, 2024)

Seasonal anthropogenic heat fluxes over 200 cities in China: An investigation of driving factors with three-dimensional building forms - Meizi Yang; Shisong Cao; Dayu Zhang; Rui Liu; Ling Cui; Yile Cai (Sustainable Cities and Society, 2024)

Transformation of metoprolol in UV/PDS process: Role and mechanisms of degradation and polymerization - Sui-Qin Yang; Rui-Qiu Ye; Yu-Hong Cui; Zheng-Qian Liu; Kai Sun; Yu-Ze Yu (Journal of Hazardous Materials, 2024)

Super Fe3+ competing ability, high biocompatibility, and mild antibacterial carbon dots for food preservation - Fangchao Cui; Rongsen Fan; Dangfeng Wang; Likun Ren; Qianqian Wang; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Tingting Li; Jianrong Li (Chemical Engineering Journal, 2024)

Orthorhombic K3V3(PO4)4: A low-temperature cathode material for potassium-ion batteries - Rui-Jie Luo; Chong-Yu Du; Cui Ma; Jie Zeng; Xuan Xu; Zhe Qian; Zhe Mei; Zi-Ting Zhou; Ze-Yu Zhu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

Ammonium addition reduces phosphorus leaching in a long-term mineral or organic fertilized calcareous soil during flooding conditions - Lulu Wei; Yan Zhou; Guiming Yin; Jianyu Cui; Junhui Yin; Rui Liu; Qing Chen; Shuai Zhang (Journal of Environmental Management, 2024)

Preparation of Fe3O4 magnetic nanomaterials for the enrichment of phosvitin phosphopeptides - Shuze Ren; Songming Li; Mahmoud Abou-Elsoud; Rui Cui; Xing Fu; Xi Huang (Food Bioscience, 2024)

Characteristics of second-hand exposure to aerosols from e-cigarettes: A literature review since 2010 - Tong Cui; Rui Lu; Chuan Liu; Zehong Wu; Xingtao Jiang; Yiqiao Liu; Song Pan; Yanpeng Li (Science of The Total Environment, 2024)

Self-assembly of metal-polyphenolic network on biomass for enhanced organic contaminant capturing from water with a high cost-to-benefit ratio - Xin Jin; Xueyi Li; Yubo Liu; Yilong Cui; Yunyi Liang; Qin Wang; Jin Wang; Rui Yang; Jianwei Zhao; Changlei Xia (Journal of Hazardous Materials, 2024)

Structural characteristics, functional properties and in vitro digestibility of rice protein prepared from rice wine lees via an alkaline extraction process or carbohydrate-lipid removal process - Xu Zhao; Rui Gao; Chun Cui; Dongxiao Sun-Waterhouse (Journal of Cereal Science, 2024)

Factors controlling accumulation and bioavailability of selenium in paddy soils: A case study in Luxi County, China - Zhangqian Xu; Weijun Zhou; Yuzhou Zhou; Haojie Cui; Rui Liu; Guiduo Shang (Environmental Pollution, 2024)

Carboxymethyl chitosan-based hydrogel-Janus nanofiber scaffolds with unidirectional storage-drainage of biofluid for accelerating full-thickness wound healing - Xinhao Chen; Hui Huang; Xinru Song; Ting Dong; Jiafei Yu; Jieyan Xu; Rui Cheng; Tingting Cui; Jun Li (Carbohydrate Polymers, 2024)

BDTX-189, a novel tyrosine kinase inhibitor, inhibits cell activity via ERK and AKT pathways in the EGFR C797S triple mutant cells - Rui Wang; Wenrui Cui; Lanxin Li; Xiangkai Wei; Chunhong Chu; Guoliang Zhang; Chenxue Liu; Huixia Xu; Chenyang Liu; Ke Wang; Yanming Li; Lei An (Chemico-Biological Interactions, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Transcriptomic and biochemical analysis of metabolic remodeling in Bacillus subtilis MSC4 under Benzo[a]pyrene stress - Rui Chen; Na Liu; Yuan Ren; Tangbing Cui (Chemosphere, 2024)

Arbuscular mycorrhizal fungi reduce ammonia emissions under different land-use types in agro-pastoral areas - Huaisong WANG; Rui GUO; Yibo TIAN; Nan CUI; Xinxin WANG; Lei WANG; Zhongbao YANG; Shuying LI; Jixun GUO; Lianxuan SHI; Tao ZHANG (Pedosphere, 2024)

Investigating the spatio–temporal characteristics of lower atmospheric ducts across the China seas by performing a long–term simulation using the WRF model - Qi Liu; Xiaofeng Zhao; Jing Zou; Tong Hu; Zhijin Qiu; Bo Wang; Zhiqian Li; Chaoran Cui; Rui Cao (Frontiers in Marine Science, 2024)
In this work, a diagnostic scheme for lower atmospheric ducts was established based on the Weather Research and Forecasting (WRF) model. More specifically, a 10-year simulation test was conducted for the China seas to investigate the spatio-temporal characteristics of the lower atmospheric ducts phenomenon. Compared with the sounding data, the long-term simulations showed a high temporal correlation and the root mean square error of the modified atmospheric refractivity remained between 4 M and 7 M. Based on the simulations, significant regional differences in the occurrence probability of lower atmospheric ducts were detected from south to north. Among them, the surface ducts near the sea surface exhibited the highest occurrence probability, with higher probabilities being recorded in autumn and winter, and the probability gradually increased with the decreasing latitude. The spatio-temporal characteristics of duct height, thickness, and strength were generally consistent. In the seas at mid-latitudes, strong ducts mostly occurred in the spring and autumn, with the single-layer ducts being predominant and the first layer duct showing stronger characteristics than the second layer. In the lower latitude regions, the situation was exactly the opposite. The first duct layer, which existed throughout the year, exhibited weaker characteristics with less pronounced seasonal variations. On the other hand, the second duct layer demonstrated stronger features.

Simulating behavior of perfluorooctane sulfonate (PFOS) in the mainstream of a river system with sluice regulations - Guoxiang Han; Shuai Song; Yonglong Lu; Meng Zhang; Di Du; Qiang Wu; Shengjie Yang; Rui Wang; Haotian Cui; Lu Yang; Ruoyu Mao; Bin Sun; et al. (Chemosphere, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Quantitative identification of the co-exposure effects of e-waste pollutants on human oxidative stress by explainable machine learning - Luhan Yang; Tao Zhang; Yanxia Gao; Dairui Li; Rui Cui; Cheng Gu; Lei Wang; Hongwen Sun (Journal of Hazardous Materials, 2024)

Endophytic Enterobacter sp. YG-14 mediated arsenic mobilization through siderophore and its role in enhancing phytostabilization - Jiawei Chen; Xuan Zhang; Min Kuang; Kunpeng Cui; Ting Xu; Xuanming Liu; Rui Zhuo; Ziwei Qin; Zhigang Bu; Zhongliang Huang; Hui Li; Jing Huang; et al. (Journal of Hazardous Materials, 2024)

Arbuscular mycorrhizal fungi offset NH3 emissions in temperate meadow soil under simulated warming and nitrogen deposition - Nan Cui; Stavros Veresoglou; Yibo Tian; Rui Guo; Lei Zhang; Li Jiang; Furong Kang; Weizhe Yuan; Dan Hou; Lianxuan Shi; Jixun Guo; Mingzhou Sun; et al. (Journal of Environmental Management, 2024)

Moment Tensor and Stress Field Inversions of Mining-Induced Seismicity in A Thick-Hard Roof Zone - Chun-Hui Song; Cai-Ping Lu; Hai-Quan Liu; Jie-Fang Song; Cheng-Yu Liu; Hua-Wei Cui; Jin-Rui Zhang (Rock Mechanics and Rock Engineering, 2024)

Spatial distribution characteristics of perfluoroalkyl substances in bulk and grain size fractionated sediments in Shenzhen Bay - Haoshuai Li; Zimin Wang; Yang Zhou; Cui Shi; Huayang Gan; Fang Chen; Lei Xing; Danxu Guo; Longhai Zhu; Nan Wang; Shuhong Fang; Rui Bao (Marine Pollution Bulletin, 2024)

Satellite observed aboveground carbon dynamics in Africa during 2003–2021 - Mengjia Wang; Philippe Ciais; Rasmus Fensholt; Martin Brandt; Shengli Tao; Wei Li; Lei Fan; Frédéric Frappart; Rui Sun; Xiaojun Li; Xiangzhuo Liu; Huan Wang; et al. (Remote Sensing of Environment, 2024)

Screening the phytotoxicity of micro/nanoplastics through non-targeted metallomics with synchrotron radiation X-ray fluorescence and deep learning: Taking micro/nano polyethylene terephthalate as an example - Hongxin Xie; Chaojie Wei; Wei Wang; Rui Chen; Liwei Cui; Liming Wang; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2024)

Hierarchical porous UiO-66 composites modified by dual competitive strategy for adsorption of oxytetracycline - Tao He; Yi Wang; Rui Han; Xiaodong Li; Shihai Cui; Jing Yang (Journal of Environmental Chemical Engineering, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

Shaking table test and numerical simulation of a precast frame-shear wall structure with innovative untopped precast concrete floors - Rui Pang; Yuan-yuan Sun; Zhu Xu; Ke Xu; Jing Cui; Long-ji Dang (Engineering Structures, 2024)

Meteorological to Agricultural Drought Propagation Time Analysis and Driving Factors Recognition Considering Time-Variant Characteristics - Chengguo Wu; Yin Xu; Juliang Jin; Yuliang Zhou; Boyu Nie; Rui Li; Yi Cui; Fei Tong; Libing Zhang (Water Resources Management, 2024)

Stytontriterpenes A−C, three unusual oleanane-derived triterpenoids from the resin of Styrax tonkinensis as potential immunosuppressive agents in atherosclerosis - Rui-Yan Jiang; Ling-Wen Yao; Yin-Hong Lv; Zhong-Tian Guo; Fei-Fei Wang; Hong-Hua Cui; Yuan-Yuan Cheng; Feng Wang (Phytochemistry, 2024)

Characterizing nitrogen dynamics and their response to sediment dredging in a lowland rural river - Qimou Zhang; Jiacong Huang; Jing Zhang; Rui Qian; Zhen Cui; Junfeng Gao (Journal of Hydrology, 2024)

Migration characteristics and local capillary trapping mechanism after the CO2 leakage out of saline aquifers - Guodong Cui; Zhe Hu; Yanyong Wang; Shu Jiang; Rui Wang (Fuel, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Tannic acid-coated cellulose nanocrystal-reinforced transparent multifunctional hydrogels with UV-filtering for wearable flexible sensors - Shuyuan Cui; Sufeng Zhang; Fengjiao Zhang; Rui Lin; Chengfang Tang; Xiaokai Jing (Carbohydrate Polymers, 2024)

Plant colorants for natural hair coloration: Dyeing optimization and photostability assessment - Hongyan Cui; Rui Cai; Zhongjie Hua; Ying Tang (Sustainable Chemistry and Pharmacy, 2023)

Design of corrosion-resistant absorbers with a core @ compact film structure based on the “dissolution-redeposition” theory - Jiaxin Qian; Yu Cui; Shucheng Ren; Rui Liu; Song Ma; Pengfei Ju; Li Liu (Chemical Engineering Journal, 2023)

Promoting reversibility of layered potassium cathode through interstitial doping - Xuan Xu; Xun-Lu Li; Muhammad Mominur Rahman; Jian Bao; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Zhe Mei; Zhe Qian; Enyuan Hu; Yong-Ning Zhou (Chemical Engineering Journal, 2023)

A review of starch swelling behavior: Its mechanism, determination methods, influencing factors, and influence on food quality - Ruoyu Jia; Congli Cui; Lin Gao; Yang Qin; Na Ji; Lei Dai; Yanfei Wang; Liu Xiong; Rui Shi; Qingjie Sun (Carbohydrate Polymers, 2023)

Calibration of the carbonate clumped isotope thermometer of land snail shells - Rui Bao; Xuefen Sheng; Chenglong Li; Can Cui; Hao Yan; Junfeng Ji; Jun Chen (Chemical Geology, 2023)

Three-dimensional visualization of the lymphatic, vascular and neural network in rat lung by confocal microscopy - Shitong Zhao; Jingjing Cui; Yuqing Wang; Dongsheng Xu; Yuxin Su; Jie Ma; Xuefeng Gong; Wanzhu Bai; Jia Wang; Rui Cao (Journal of Molecular Histology, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

The discrimination of tectonic settings using trace elements in magmatic zircons: A machine learning approach - Luyuan Wang; Chao Zhang; Rui Geng; Yuqi Li; Jijie Song; Bin Wang; Fanghua Cui (Earth Science Informatics, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Aluminum soap nanoparticles-lignin powder form phase-selective gelator as an efficient sorbent for oils/water separation - Suwan Cui; Bohao Qi; Hao Liu; Xiaojun Sun; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Mutai Bao (Chemosphere, 2023)

A method for obtaining maize phenotypic parameters based on improved QuickShift algorithm - Rui Gao; Shangqing Cui; HaoRan Xu; Qingming Kong; Zhongbin Su; Jinlong Li (Computers and Electronics in Agriculture, 2023)

PM1 exposure and spatial transmission of nicotine from the simulated second-hand vapor of pod-based electronic cigarettes - Tong Cui; Rui Lu; Qianyun Liu; Xingtao Jiang; Yanpeng Li; Song Pan (Science of The Total Environment, 2023)

Different responses of precipitation patterns to the East Asian summer monsoon weakening: The 7.2 and 8.2 ka events - Liangkang Pan; Jingyao Zhao; Yan Yang; Kexin Wang; Carlos Pérez-Mejías; Jiahui Cui; Xiyu Dong; Rui Zhang; Hai Cheng (Quaternary Science Reviews, 2023)

Occurrences of typical PPCPs during wastewater treatment and the composting of sewage sludge with micron-sized and nano-sized Fe3O4 - Jishao Jiang; Rui Hou; Huilin Cui; Dong Liu; Guangxuan Yan; Yujuan Fan; Ke Cheng; Zhiguo Cao (Environmental Pollution, 2023)

Enhancing biomass oxidation with carbon nitride nanosheets ring inserted on C. I. Pigment Yellow 53 photocatalysts for simultaneous CO and lactic acid production - Weikang Ling; Jiliang Ma; Zhendong Liu; Rui Cui; Junqiang Zhang; Xinze Li; Min Hong; Runcang Sun (Chemical Engineering Journal, 2023)

Efficient and effective immobilization of tetracycline and copper from wastewater by zero-valent iron fabricated hydrochar derived from walnut peel - Huabin Wang; Dingxiang Chen; Ting Cui; Ran Duan; Xianghong Yan; Yong Zhang; Rui Xu (Bioresource Technology, 2023)

Source and migration patterns of heavy metals and human health risk assessment of heavy metals in soil-corn straw-flue gas system - Yongbo Cui; Li Bai; Chunhui Li; Rui Du (Environmental Geochemistry and Health, 2023)

Human amnion-derived mesenchymal stem cells improve subclinical hypothyroidism by immunocompetence mediating apoptosis inhibition on thyroid cells in aged mice - Chuyu Li; Qiang Rui; Xiaohan Dong; Song Ning; Jing Zhou; Huimin Wu; Chunyan Jiang; Yugui Cui; Jiayin Liu; Jun Jiang; Lianju Qin (Cell and Tissue Research, 2023)
Subclinical hypothyroidism (SCH) affects 10% of the global population, which is most prevalent in women and the elderly. However, it remains debatable whether the elderly with subclinical hypothyroidism needs thyroxine supplement. Human amnion-derived mesenchymal stem cells (hAMSCs) could play important roles in autoimmune diseases, suggesting that hAMSC be a candidate to regulate the thyroid function of female age-related subclinical hypothyroidism. Herein, we established the model of SCH in the aged female mice. This study was designed to investigate whether human amnion-derived mesenchymal stem cells (hAMSC) could effect on immune regulation, apoptosis inhibition of thyroid cells, thyroid function, blood lipid levels, and heart function. In addition, qualified hAMSCs were intravenously injected into aged female SCH mice via the tail vein on day 0 and day 10. The levels of thyroid hormone and blood lipids as well as cardiac function, serum immunological indexes, and apoptosis of thyroid cells were then analyzed on day 5, 10, 15, and 20; meanwhile, the quantity of Th1, Th2, Th17, and Treg immune cells in peripheral blood was evaluated before and on day 20 post-injection. Our study demonstrated that after hAMSC transplantation, the thyroid functions, blood lipid levels, and heart function indexes of age-related SCH (AR-SCH) mice were significantly improved. Consistent with this, Th1 and Treg cells increased significantly, while Th2 and Th17 cells decreased in peripheral blood. Apoptosis was also suppressed in the thyroid cells. In summary, hAMSC delivery can potentially be a safe and effective therapy for treating SCH in the elderly, improving related complications by immunomodulatory and apoptosis inhibition.

Melt-blown fiber felt for efficient all-weather recovery of viscous oil spills by Joule heating and photothermal effect - Bohao Qi; Nuo Wang; Xin Hu; Suwan Cui; Hao Liu; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Yang Li; Mutai Bao (Journal of Hazardous Materials, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Comprehensive investigation of milk oligosaccharides in different mammalian species and the effect of breed and lactation period on sheep milk oligosaccharides - Haiyan Wang; Minghui Zhang; Yucui Huo; Xiuxiu Cui; Rui He; Bei Han; Zhongfu Wang; Yuxuan Song; Xin Lv; Jing Zhang; Wupeng Ge (Food Research International, 2023)

Fe/N-doped carbon dots-based nanozyme with super peroxidase activity, high biocompatibility and antibiofilm ability for food preservation - Fangchao Cui; Lanling Li; Dangfeng Wang; Likun Ren; Jiesen Li; YiLin Lu; Yuqiong Meng; Rui Ma; Shulin Wang; Xuepeng Li; Tingting Li; Jianrong Li (Chemical Engineering Journal, 2023)

Emission accounting and drivers in Central Asian countries - Congyu Zhao; Binyuan Liu; Jieyu Wang; Rui Xue; Yuli Shan; Can Cui; Xiucheng Dong; Kangyin Dong (Environmental Science and Pollution Research, 2023)
Emerging countries are at the frontier of climate change actions, and carbon emissions accounting provides a quantifiable measure of the environmental impact of economic activities, which allows for comparisons of emissions across different entities. However, currently there is no study covering detailed emissions inventories for emerging countries in Central Asian. This paper compiles detailed and accurate carbon emissions inventories in several Central Asian countries (i.e., Kazakhstan, Kyrgyzstan, Pakistan, Palestine, Tajikistan, and Uzbekistan) during the period 2010–2020. Using the IPCC administrative territorial approach, we for the first time compile their emissions inventories in 47 economic sectors and five energy categories. Moreover, we also investigate decoupling status based on Tapio decoupling model and examine emissions driving factors based on the index decomposition analysis method. The primary results illustrate that carbon emissions in Central Asian countries are increasing with huge differences. Decoupling results highlight that most of the sample countries still need more effort to decouple the economy and emissions except that Pakistan achieves an ideal strong decoupling state. The results of the decomposition indicate that the economy and population both raise emissions, while energy intensity and carbon intensity are negative drivers in some countries. We propose practical policy implications for decarbonization and energy transition roadmap in Central Asian countries.

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Spatiotemporal variation in soil methane uptake in a cool-temperate immature deciduous forest - Rui Hu; Takashi Hirano; Kaho Sakaguchi; Syunpei Yamashita; Rui Cui; Lifei Sun; Naishen Liang (Soil Biology and Biochemistry, 2023)

Variations in trihalomethane formation potential of Microcystis aeruginosa under different growth conditions: Phenomenon and mechanism - Rui Huang; Wenbo Guo; Zhiquan Liu; Shugeng Li; Zhiwei Zhao; Wenxin Shi; Fuyi Cui; Chun Hu (Science of The Total Environment, 2023)

Exfoliation behavior and superior photothermal conversion performance of MXenes beyond Ti3C2T - Cuilian Wen; Qiugang Liao; Zhou Cui; Ziqiang Chen; Hao Liu; Rui Xiong; Baisheng Sa (Chemical Engineering Journal, 2023)

Ultrasonic-assisted hypochlorite activation accelerated volatile fatty acids production during sewage sludge fermentation: Critical insights on solubilization/hydrolysis stages and microbial traits - Rui Zhu; Shanshan Zhao; Chenlu Ju; Qing Yang; Chengcheng Cui; Lijuan Wu; Min Wang; Leiyu Feng; Yang Wu (Bioresource Technology, 2023)

Laboratory simulation of CO2 immiscible gas flooding and characterization of seepage resistance - Jie Chi; Binshan Ju; Wenbin Chen; Mengfei Zhang; Rui Zhang; Anqi Miao; Dayan Wang; Fengyun Cui (Frontiers of Earth Science, 2023)

Impact of rhizosphere priming on soil organic carbon dynamics: Insights from the perspective of carbon fractions - Hao Cui; Chaoyang Mo; Pengfei Chen; Rui Lan; Chao He; Jingdong Lin; Zhenhui Jiang; Jingping Yang (Applied Soil Ecology, 2023)

A precise crop row detection algorithm in complex farmland for unmanned agricultural machines - Zhiwen Ruan; Penghao Chang; Shangqing Cui; Jiaqi Luo; Rui Gao; Zhongbin Su (Biosystems Engineering, 2023)

Study on high-value products of waste plastics from microwave catalytic pyrolysis: Construction and performance evaluation of advanced microwave absorption-catalytic bifunctional catalysts - Juan Luo; Guojin Gong; Rui Ma; Shichang Sun; Chongwei Cui; Han Cui; Jiaman Sun; Ning Ma (Fuel, 2023)

Effect of a novel joint connection of UHPC wet joint and tapered sleeve locking-type couplers on the lateral cyclic response of precast segmental railway bridge columns - Yuxuan Wang; Zhao Cheng; Shuai Li; Jingquan Wang; Rui Zhong; Min Zeng; Fayan Ming; Bing Cui (Engineering Structures, 2023)

Source analysis of metals in the tea plant using linear correlation analysis combined with a lead-strontium isotope tracer - Yan Cong; Rui-lian Yu; Yu Yan; Bo-sen Weng; Gong-ren Hu; Jing-wei Sun; Jian-yong Cui; YanYan; Yao-yi Huang (CATENA, 2023)

Multimedia fate of sulfamethoxazole (SMX) in a water-scarce city by coupling fugacity model and HYDRUS-1D model - Yanqi Wu; Shuai Song; Fadong Li; Haotian Cui; Rui Wang; Shengjie Yang; Zhao Li; Gang Chen (Science of The Total Environment, 2023)

Enhanced desalination performances by using porous polyaniline-activated carbon composite flow-electrodes in capacitive deionization system - Rui Chen; Xiaoyong Deng; Chuang Wang; Jinying Du; Zhiwei Zhao; Wenxin Shi; Fuyi Cui; Changyong Zhang (Desalination, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

Effect of exogenous Ca on the physiology and growth indicators of pakchoi under foliar and root fluorine stress - Rui Liu; Si-fan Cui; Chun-dan Gan; Jin-yan Yang (Environmental Geochemistry and Health, 2023)

Study on the feasibility of carbon source recovery by upflow anaerobic sludge blanket in simulated municipal wastewater - Xiao Zhang; Bowei Zhao; Rui Li; Ying Cui; Fei Xie; Aijuan Zhou; Jinping Li; Xiuping Yue (Science of The Total Environment, 2023)

Insight into micropollutant abatement during ultraviolet light-emitting diode combined electrochemical process: Reaction mechanism, contributions of reactive species and degradation routes - Rui Hu; Sui-Qin Yang; Jia-Ying Li; Fengyi Sun; Zheng-Qian Liu; Jingjing Yang; Yu-Hong Cui; Beiping Zhang (Science of The Total Environment, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Sensing property of Pt-doped Janus SnSSe monolayer upon thermal runaway gases in the lithium-ion battery with effects of biaxial strains and electric fields - Di Zheng; Wenjing Peng; Rui Wu; Shunan Quan; Lijuan Qian; Hao Cui (Journal of Environmental Chemical Engineering, 2023)

Use of nano titanium hydroxide and nano zirconium hydroxide fixed filter paper for rapid detection of Staphylococcus aureus in dairy products by PCR without pre-enrichment - Chun Wang; Ruohong Zhang; Xiaofang Wang; Rui Xu; Hejing Yan; Xiaoran Li; Shaojun Liu; Shuren Yin; Hong Yao; Yang Yang; Shenghui Cui; Yunchang Guo (Food Control, 2023)

A novel fluidized-bed-electrode solid-oxide-fuel-cell reactor for N2O catalytic decomposition - Dongxu Cui; Shiliang Wu; Tao Li; Yuxin Zhang; Sang Jun Yoon; Youn-Sang Bae; Bugae Park; Yinlong Wu; Rui Xiao (Chemical Engineering Journal, 2023)

Understanding the process of phosphate removal in Fe0/H2O systems using the methylene blue method - Bernard Konadu-Amoah; Rui Hu; Xuesong Cui; Ran Tao; Arnaud Igor Ndé-Tchoupé; Willis Gwenzi; Chicgoua Noubactep (Chemical Engineering Journal, 2023)

Production of antifungal iturins from vegetable straw: A combined chemical-bacterial process - Yuan Yuan; Depeng Chu; Jiajun Fan; Zhenzhen Cui; Rui Wang; Han Zhang; Xiangwei You; Yiqiang Li; Xiaoqiang Wang (Bioresource Technology, 2023)

Simultaneously mapping loci related to two plant architecture traits by phenotypic recombination BSA/BSR in peanut (Arachis hypogaea L.) - Xiaona Yu; Yaoyao Li; Xinyuan Cui; Xianheng Wang; Jihua Li; Rui Guo; Fanzhuang Yan; Shaojing Zhang; Ruihua Zhao; Danlei Song; Tong Si; Xiaoxia Zou; et al. (Theoretical and Applied Genetics, 2023)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

Elemental Geochemical Distribution of the Jurassic Yan'an Formation in the Ningdong Coalfield and its Controlling Effect on Coal Reservoir Properties - Jincheng Ye; Yafei Zhang; Wei He; Rui Tao; Shu Tao; Shida Chen; Yi Cui; Qi Wang (Natural Resources Research, 2023)

Competitive adsorption of lead and cadmium onto nanoplastics with different charges: Two-dimensional correlation spectroscopy study - Tao Li; Xiufeng Cao; Xiaowei Cui; Rui Zhao; Huayi Chen; Wenxiu Xue; Zhaojie Cui; Xianfeng Tan; Shouqing Ni (Environmental Science and Pollution Research, 2023)

In-situ preparation of yeast-supported Fe0@Fe2O3 as peroxymonosulfate activator for enhanced degradation of tetracycline hydrochloride - Bin Li; Chen-Xuan Li; Yan Wang; Weiyi Xu; Kangping Cui; Xinyuan Zhan; Rui Deng; Xing Zhang (Chemosphere, 2023)

Hormesis effects of sulfoxaflor on Aphis gossypii feeding, growth, reproduction behaviour and the related mechanisms - Li Wang; Junshu Zhu; Qinqin Wang; Xuejiao Ji; Wenjie Wang; Weiling Huang; Changhui Rui; Li Cui (Science of The Total Environment, 2023)

Integrative effects of microbial inoculation and amendments on improved crop safety in industrial soils co-contaminated with organic and inorganic pollutants - Xiaowei Cui; Xiufeng Cao; Wenxiu Xue; Lei Xu; Zhaojie Cui; Rui Zhao; Shou-Qing Ni (Science of The Total Environment, 2023)

Exposure to real-ambient particulate matter induced vascular hypertrophy through activation of PDGFRβ - Hongxu Bao; Benying Li; Qing You; Xinyu Dun; Zhen Zhang; Yanan Liang; Yahui Li; Qixiao Jiang; Rong Zhang; Rui Chen; Wen Chen; Yuxin Zheng; et al. (Journal of Hazardous Materials, 2023)

Theoretical study the electrocatalytic performance and mechanism of novel designed electrocatalyst Ru@2DMs for CO2RR - Linxia Cui; Ke Shi; Mingyuan Zhang; Jiuwen Guo; Zhe Yan; Haigang Hao; Rui Gao (Fuel, 2023)

Mechanistic studies of polyphenols reducing the trypsin inhibitory activity of ovomucoid: Structure, conformation, and interactions - Rui Cui; Shengnan Ji; Minquan Xia; Xing Fu; Xi Huang (Food Chemistry, 2023)

Intelligent recognition of spacecraft components from photorealistic images based on Unreal Engine 4 - Yunpeng Zhao; Rui Zhong; Linyan Cui (Advances in Space Research, 2023)

Forward osmosis membrane doped with water-based zirconium fumarate MOFs to enhance dye pollutant removal and membrane antifouling performance - Miaolu He; Leihao Feng; Qi Cui; Yushuang Li; Jiaqi Wang; Jiani Zhu; Lei Wang; Xudong Wang; Rui Miao (Environmental Science and Pollution Research, 2023)

Sulfoxaflor adversely influences the biological characteristics of Coccinella septempunctata by suppressing vitellogenin expression and predation activity - Li Wang; Yanhui Zhai; Junshu Zhu; Qinqin Wang; Xuejiao Ji; Wenjie Wang; Huizhu Yuan; Changhui Rui; Li Cui (Journal of Hazardous Materials, 2023)

Crushing combined with high–frequency turning can promote material degradation of sheep manure compost on the Qinghai–Tibet Plateau by improving the microbial metabolic function - Rui Cai; Xinyu Cui; Xiaohui Cao; Xin Jiang; Rongze Wang; Chuncheng Xu (Journal of Environmental Chemical Engineering, 2023)

The interaction mechanism and the functionality of yeast protein with hydrophilic and hydrophobic bioactive molecules - Haili Sun; Yifei Sun; Xin Tang; Yuanmeng Cui; Demei Meng; Yuyu Zhang; Ku Li; Hui Guo; Hai Chen; Rui Yang (Food Bioscience, 2023)

Boosting photocatalytic ammonia synthesis performance over OVs-Rich Ru/W18O49: Insights into the roles of oxygen vacancies in enhanced hydrogen spillover effect - Lulu Zhang; Rui Li; Luyao Cui; Zijun Sun; Lijun Guo; Xiaochao Zhang; Yunfang Wang; Yawen Wang; Zhuobin Yu; Tao Lei; Xuan Jian; Xiaoming Gao; et al. (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Bone marrow mesenchymal stem cells derived exosomal Lnc TUG1 promotes bone fracture recovery via miR-22-5p/Anxa8 axis - Wei Li; Lihong Li; Rui Cui; Xiaoqing Chen; Haifeng Hu; Yuyu Qiu (Human Cell, 2023)
Bone fracture healing is a complex physiologic process that involves changes in the expression of several thousand genes. Long noncoding RNAs (lncRNAs) may have critical biological roles in this process. The objectives of the present study were to determine whether BMSC-derived exosomal lncTUG1 can enhance osteogenic differentiation and thereby promoting bone fracture recovery and to investigate its potential mechanisms of action. Bone marrow mesenchymal stromal cells were isolated from mice and cultured for the following experiments. After adipogenic and osteogenic differentiation induction, Oil Red O, alizarin red S, and alkaline phosphatase staining solutions were applied to confirm the formation of lipid droplets and calcium nodules. Western blotting analyses, real-time reverse transcription PCR assays, luciferase reporter were performed to confirm relative RNA and protein expressions and luciferase activities of transfected cells. RNA pull-down and RNA immunoprecipitation assays were also carried to verify the interaction between lncTUG1 and miR-22-5p. Additionally, a mouse model of closed femoral fractures was generated to evaluate the in vivo effect of increased lncTUG1 on fracture healing. BMSC-derived exosomal lncTUG1 enhanced the activity of osteoblasts. Overexpression of miR-22-5p reversed the osteopromoting effect of increased lncTUG1. The knockdown of Anxa8 reversed the osteogenic effect of miR-22-5p inhibitors, indicating an interaction between Anxa8 and miR-22-5p. Upregulation of lncTUG1 could promote the fracture recovery in vivo. In conclusion, the present study highlights the functional importance of BMSC-derived exosomal lncTUG1 in the process of bone fracture recovery.

Circ_0021573 acts as a competing endogenous RNA to promote the malignant phenotypes of human ovarian cancer cells - Lifang Liu; Bingkai Han; Lixia Liu; Hongying Cui; Hao Liu; Rui Jia; Xiaoyan Zhang; Xiaoxiao Lu (Reproductive Biology, 2023)

SUMOylation-modified Pelota-Hbs1 RNA surveillance complex restricts the infection of potyvirids in plants - Linhao Ge; Buwei Cao; Rui Qiao; Hongguang Cui; Shaofang Li; Hongying Shan; Pan Gong; Mingzhen Zhang; Hao Li; Aiming Wang; Xueping Zhou; Fangfang Li (Molecular Plant, 2023)

Corrigendum to “A review of salt precipitation during CO2 injection into saline aquifers and its potential impact on carbon sequestration projects in China” [Fuel 334 (2022) 126615] - Guodong Cui; Zhe Hu; Fulong Ning; Shu Jiang; Rui Wang (Fuel, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Highly sensitive surface-enhanced Raman scattering (SERS) imaging for phenotypic diagnosis and therapeutic evaluation of breast cancer - Chonggui Qiu; Wei Zhang; Yanhong Zhou; Hongwang Cui; Yanlong Xing; Fabiao Yu; Rui Wang (Chemical Engineering Journal, 2023)

Selenium alleviates endoplasmic reticulum calcium depletion-induced endoplasmic reticulum stress and apoptosis in chicken myocardium after mercuric chloride exposure - Pei-Chao Gao; An-Qi Wang; Xue-Wei Chen; Han Cui; Yue Li; Rui-Feng Fan (Environmental Science and Pollution Research, 2023)

Ecological toxicity of Cd, Pb, Zn, Hg and regulation mechanism in Solanum nigrum L. - Rui Zhao; Xiufeng Cao; Xinxin Li; Tao Li; Hong Zhang; Xiaowei Cui; Zhaojie Cui (Chemosphere, 2023)

Modeling on cryogenic heat exchangers considering variable properties, axial heat conduction and viscous heating - Xue-shuo Shang; Zhuo Miao; Huai-qing Cao; Rui Wang; Wei Shao; Zheng Cui (International Journal of Refrigeration, 2023)

A review of salt precipitation during CO2 injection into saline aquifers and its potential impact on carbon sequestration projects in China - Guodong Cui; Zhe Hu; Fulong Ning; Shu Jiang; Rui Wang (Fuel, 2023)

Metagenomic insights into bacterial communities and functional genes associated with texture characteristics of Kazakh artisanal fermented milk Ayran in Xinjiang, China - Malina Kuerman; Rui Wang; Yu Zhou; Xiaoying Tian; Qingyu Cui; Huaxi Yi; Pimin Gong; Zhe Zhang; Kai Lin; Tongjie Liu; Lanwei Zhang (Food Research International, 2023)

Methyl 4-hydroxybenzoate nanospheres anchored on poly(amidoxime)/polyvinyl alcohol hydrogel network with excellent antibacterial activity for efficient uranium extraction from seawater - Junqiang Zhang; Jiliang Ma; Gaojie Jiao; Kangning Liu; Rui Cui; Shangru Zhai; Runcang Sun (Desalination, 2023)

Facile fabrication of flexible and ultrathin self-assembled Ti3C2T /bacterial cellulose composite films with multifunctional electromagnetic shielding and photothermal conversion performances - Hao Liu; Zhou Cui; Lijin Luo; Qiugang Liao; Rui Xiong; Chao Xu; Cuilian Wen; Baisheng Sa (Chemical Engineering Journal, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

Bioaccessibility and bioavailability evaluation of heavy metal(loid)s in ginger in vitro: Relevance to human health risk assessment - Xin Xu; Jinhang Wang; Huihui Wu; Rui Lu; Jun Cui (Science of The Total Environment, 2023)

Soil microbial community structure dynamics shape the rhizosphere priming effect patterns in the paddy soil - Hao Cui; Pengfei Chen; Chao He; Zhenhui Jiang; Rui Lan; Jingping Yang (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Scaled-up microwave pyrolysis of sludge for hydrogen-rich biogas and life cycle assessment: Parameters synergistic optimization, carbon footprint analysis and technology upgrade - Junhao Lin; Shiwei Liu; Zijian Han; Rui Ma; Chongwei Cui; Shichang Sun (Chemical Engineering Journal, 2023)

Rationally tailoring anion traps into electrospun nanofibers for highly efficient perrhenate/pertechnetate capture - Dingyang Chen; Zhaoli Liu; Shuying Li; Xiaofei Jing; Yuyang Tian; Wei Hu; Fengchao Cui; Rui Zhao; Guangshan Zhu (Chemical Engineering Journal, 2023)

Enhancing structural and cycle stability of Prussian blue cathode materials for calcium-ion batteries by introducing divalent Fe - Chong-Yu Du; Zi-Hao Zhang; Xun-Lu Li; Rui-Jie Luo; Cui Ma; Jian Bao; Jie Zeng; Xuan Xu; Fei Wang; Yong-Ning Zhou (Chemical Engineering Journal, 2023)

Iron-tungsten oxides modified oxygen-rich carbon nitride with defects S-scheme heterojunction for boosting photo-Fenton like removal of pollutants - Xiaoyong Deng; Rui Chen; Chuang Wang; Zhijie Liang; Zhiwei Zhao; Wenxin Shi; Fuyi Cui (Chemical Engineering Journal, 2023)

Partitioning of root respiration into growth, maintenance, and ion uptake components in a young larch-dominated forest - Takashi Hirano; Rui Cui; Lifei Sun; Munemasa Teramoto; Naishen Liang (Plant and Soil, 2023)

Environmental and economic benefits of substituting chemical potassium fertilizer with crop straw residues in China - Junhui Yin; Dongjia Li; Jingyao Yu; Xin Bai; Wenjing Cui; Rui Liu; Minghao Zhuang (Environmental Science and Pollution Research, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

SLAH1 is involved in the long-distance transport of Cl− from roots into shoots in the Cl−-tolerant xerophyte Pugionium cornutum under salt stress - Yan-Nong Cui; Xiao-Yu Li; Rui-Wen Liu; Zi-Hua He; Suo-Min Wang; Qing Ma (Plant and Soil, 2022)

Aluminum-activated Malate Transporter 12 is involved in restricting root-to-shoot Cl− transport in Arabidopsis under Cl−-salt stress - Rui-Wen Liu; Jian-Zhen Yuan; Xiao-Yu Li; Yan-Nong Cui; Mei-Mei Cai; Zi-Hua He; Qing Ma (Plant and Soil, 2022)

Where did Yunnan’s puddling steel technology come from? Preliminary analysis of metallurgical relics unearthed from the Shushi Ancient City Site in Zhaotong, Yunnan Province, China - Guisen Zou; Rui Min; Ranchao Zhou; Jianfeng Cui (Archaeological and Anthropological Sciences, 2022)

RNAi-Based Transcriptome Suggests Candidate Genes Regulated by ZxNHX1 to Affect The Salt Tolerance of Zygophyllum xanthoxylum - Hai-Shuang Liu; Xiao-Nong Guo; Wei-Wei Chai; Rui-Xin Zhang; Pei-Qin Li; Cui-Min Ma; Qing Ma; Suo-Min Wang (Journal of Plant Growth Regulation, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Genetically encoded redox biosensor system for H2O2 measurement in four subcellular compartments in acute myeloid leukemia (AML) cells - Mengmeng Cui; Ghulam Abbas; Dianbing Wang; Qian Liu; Rui Gong; Min Li; Xian-En Zhang (Science China Life Sciences, 2022)

Neuregulin-1 regulates the conversion of M1/M2 microglia phenotype via ErbB4-dependent inhibition of the NF-κB pathway - Yuqi Ma; Peixia Fan; Rui Zhao; Yinghua Zhang; Xianwei Wang; Weigang Cui (Molecular Biology Reports, 2022)

Antibiotic resistomes in water supply reservoirs sediments of central China: main biotic drivers and distribution pattern - Kai Zhang; Kuangjia Li; Rui Xin; Ya Han; Ziwei Guo; Wei Zou; Wei Wei; Xiangchao Cui; Zhongshuai Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Geochronological, geochemical, and P–T path constraints on the late Paleoproterozoic continent–continent collision orogeny in the Quruqtagh Block, Tarim Craton - Tao Cui; Shan-Shan Li; Rui-Qing Guo; Germain Bishikwabo; Xiang-Kuan Gong; Gui-Ping Liu; Yu Guo (Arabian Journal of Geosciences, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

A switch-on molecular biosensor for detection of caspase-3 and imaging of apoptosis of cells - Rui Gong; Dianbing Wang; Ghulam Abbas; Shimin Li; Qian Liu; Mengmeng Cui; Xian-En Zhang (Science China Life Sciences, 2022)

Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Yajuan Gao; Hongbin Han; Jichen Du; Qingyuan He; Yanxing Jia; Junhao Yan; Hui Dai; Bin Cui; Jing Yang; Xunbin Wei; Liu Yang; Rui Wang; et al. (Science China Life Sciences, 2022)

Sulfoxaflor resistance in Aphis gossypii: resistance mechanism, feeding behavior and life history changes - Li Wang; Li Cui; Qinqin Wang; Yanpeng Chang; Weiling Huang; Changhui Rui (Journal of Pest Science, 2022)

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

Magnolol upregulates CHRM1 to attenuate Amyloid-β-triggered neuronal injury through regulating the cAMP/PKA/CREB pathway - Gemin Zhu; Yuan Fang; Xiaoli Cui; Ruihua Jia; Xiaogang Kang; Rui Zhao (Journal of Natural Medicines, 2022)

Role of low-carbon technology innovation in environmental performance of manufacturing: evidence from OECD countries - Rui Shi; Yu Cui; Minjuan Zhao (Environmental Science and Pollution Research, 2021)

Experimental Observations of Gas-sorption-Induced Strain Gradients and their Implications on Permeability Evolution of Shale - Rui Shi; Jishan Liu; Xiaoming Wang; Derek Elsworth; Zhizhuang Wang; Mingyao Wei; Guanglei Cui (Rock Mechanics and Rock Engineering, 2021)

Fast and accurate detection of kiwifruit in orchard using improved YOLOv3-tiny model - Longsheng Fu; Yali Feng; Jingzhu Wu; Zhihao Liu; Fangfang Gao; Yaqoob Majeed; Ahmad Al-Mallahi; Qin Zhang; Rui Li; Yongjie Cui (Precision Agriculture, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

Modeling and insights into molecular basis of low molecular weight respiratory sensitizers - Xueyan Cui; Rui Yang; Siwen Li; Juan Liu; Qiuyun Wu; Xiao Li (Molecular Diversity, 2021)

High-resolution estimation of ambient sulfate concentration over Taiwan Island using a novel ensemble machine-learning model - Lulu Cui; Qingwei Ma; Rui Li; Hongbo Fu; Ziyu Zhang; Liwu Zhang; Ying Chen (Environmental Science and Pollution Research, 2021)

A Rehmannia glutinosa cinnamate 4-hydroxylase promotes phenolic accumulation and enhances tolerance to oxidative stress - Yan Hui Yang; Heng Yang; Rui Fang Li; Cui Xiang Li; Lei Zeng; Chao Jie Wang; Na Li; Zhuang Luo (Plant Cell Reports, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Formaldehyde-induced hematopoietic stem and progenitor cell toxicity in mouse lung and nose - Yun Zhao; Laura C. Magaña; Haiyan Cui; Jiawei Huang; Cliona M. McHale; Xu Yang; Mark R. Looney; Rui Li; Luoping Zhang (Archives of Toxicology, 2021)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Effects of Cr(VI)-reducing bacteria on the behaviour of Cr(VI) adsorption by goethite and haematite: speciation and distribution - Chunyong Wang; Rui Wu; Jianbo Guo; Yanshan Cui (Journal of Soils and Sediments, 2020)

Graph-based network analysis of resting-state fMRI: test-retest reliability of binarized and weighted networks - Jie Xiang; Jiayue Xue; Hao Guo; Dandan Li; Xiaohong Cui; Yan Niu; Ting Yan; Rui Cao; Yao Ma; Yanli Yang; Bin Wang (Brain Imaging and Behavior, 2020)

Isolation and functional characterization of the mitogen-activated protein kinase kinase gene MAPKK1 from Panax notoginseng - Limei Pu; Rui Chen; Shah Taif; Qin Zhao; Xin Li; Yuan Qu; Xiuming Cui; Diqiu Liu (European Journal of Plant Pathology, 2020)

Neurofeedback Training for Brain Functional Connectivity Improvement in Mild Cognitive Impairment - Xin Li; Jie Zhang; Xiang-Dong Li; Wei Cui; Rui Su (Journal of Medical and Biological Engineering, 2020)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

Quantitative proteomic analysis reveals that the Rap1/MAPK/ERK pathway is inhibited through selenomethionine strengthening antioxidant activity - Zhe Liu; Feng Zhang; Lina Cui; Jihong Wang; Ping Lu; Rui Zhao; Hua Zhang; Jianfa Wang; Chunqiu Li; Rui Wu (BioMetals, 2020)

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Antioxidative and Probiotic Activities of Lactic Acid Bacteria Isolated from Traditional Artisanal Milk Cheese from Northeast China - Yunjia Shi; Xingyang Cui; Shanshan Gu; Xin Yan; Rui Li; Shuang Xia; Hongyan Chen; Junwei Ge (Probiotics and Antimicrobial Proteins, 2019)

A transcriptome analysis uncovers Panax notoginseng resistance to Fusarium solani induced by methyl jasmonate - Diqiu Liu; Qin Zhao; Xiuming Cui; Rui Chen; Xin Li; Bingling Qiu; Feng Ge (Genes & Genomics, 2019)

HprK Xcc is a serine kinase that regulates virulence in the Gram‐negative phytopathogen Xanthomonas campestris - Rui‐Fang Li; Ping Cui; Ping‐Zhen Wei; Xing‐Yan Liu; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2019)
Summary The HprK serine kinase is a component of the phosphoenolpyruvate phosphotransferase system (PTS) of bacteria that generally regulates catabolite repression through phosphorylation/dephosphorylation of the PTS protein PtsH at a conserved serine residue. However, many bacteria do not encode a complete PTS or even have an HprK homologue. Xanthomonas campestris pv. campestris ( Xcc ) is a pathogen that cause black rot disease in crucifer plants and one of the few Gram‐negative bacteria that encodes a homologue of HprK protein (herein HprK Xcc ). To gain insight into the role of HprK Xcc and other PTS‐related components in Xcc we individually mutated and phenotypically assessed the resulting strains. Deletion of hprK Xcc demonstrated its requirement for virulence and other diverse cellular processes associated including extracellular enzyme activity, extracellular‐polysaccharide production and cell motility. Global transcriptome analyses revealed the HprK Xcc had a broad regulatory role in Xcc . Additionally, through overexpression, double gene deletion and transcriptome analysis we demonstrated that hprK Xcc shares an epistatic relationship with ptsH . Furthermore, we demonstrate that HprK Xcc is a functional serine kinase, which has the ability to phosphorylate PtsH. Taken together, the data illustrates the previously unappreciated global regulatory role of HprK Xcc and previously uncharacterized PTS components that control virulence in this pathogen.

The basolateral amygdala regulation of complex cognitive behaviours in the five-choice serial reaction time task - Fangyuan Yin; Hao Guo; Jingjing Cui; Yuhui Shi; Rui Su; Qiaoli Xie; Jinrui Chang; Yunpeng Wang; Jianghua Lai (Psychopharmacology, 2019)

Two new polyketides isolated from a diethyl sulphate mutant of marine-derived Penicillium purpurogenum G59 - Chang-Jing Wu; Hua Qiao; Cheng-Bin Cui; Yu Yang; Rui Xu; Chun-Xiao Sun; De-Hai Li; Chang-Wei Li (Natural Product Research, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

The origin and distribution of Ordovician Yingshan dolomite on the northern slope of Tazhong area in Tarim Basin - Zhao Jiahui; Zhao Rui; Wu Yasheng; Liu Tianjia; Cui Xuemin; Guo Kunzhang (Carbonates and Evaporites, 2019)

Three Tibetan grassland plant species tend to partition niches with limited plasticity in nitrogen use - Li Zhang; Rui Pang; Xingliang Xu; Minghua Song; Yikang Li; Huakun Zhou; Xiaoyong Cui; Yanfen Wang; Hua Ouyang (Plant and Soil, 2019)

Comparison of PAH content, potential risk in vegetation, and bare soil near Daqing oil well and evaluating the effects of soil properties on PAHs - Xin Li; Rui Zheng; Qinghua Bu; Qinghai Cai; Yufen Liu; Qian Lu; JiZhe Cui (Environmental Science and Pollution Research, 2019)

Two new sesquiterpenes from cultures of the higher fungus Pholiota nameko - Xiao-Yan Yang; Wan-Rong Niu; Rui-Ting Li; Xiu-Ming Cui; Ji-Kai Liu (Natural Product Research, 2019)

Study on the denitrification performance of FexLayOz/activated coke for NH3-SCR and the effect of CO escaped from activated coke at mid-high temperature on catalytic activity - Jiaqing Wang; Pei Lu; Wei Su; Yi Xing; Rui Li; Yuran Li; Tingyu Zhu; Huifang Yue; Yongkang Cui (Environmental Science and Pollution Research, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Spatiotemporal extremes of temperature and precipitation during 1960–2015 in the Yangtze River Basin (China) and impacts on vegetation dynamics - Lifang Cui; Lunche Wang; Sai Qu; Ramesh P. Singh; Zhongping Lai; Rui Yao (Theoretical and Applied Climatology, 2019)

A new polyketide purpurogenic acid: the activated production of polyketides by the diethyl sulphate mutagenesis of marine-derived Penicillium purpurogenum G59 - Ming-Wen Xia; Yu Yang; Rui Xu; Chang-Wei Li; Cheng-Bin Cui (Natural Product Research, 2019)

Flavonoid glucosides from the flowers of Trollius chinensis Bunge - Rui Yan; Yida Cui; Bowen Deng; Jiayi Bi; Guogang Zhang (Journal of Natural Medicines, 2019)

Investigation of early Bronze Age civilizations in Yunnan: a scientific analysis of metallurgical relics found at the Guangfentou ruins in Jiangchuan - Guisen Zou; Jianfeng Cui; Xu Liu; Xiaorui Li; Rui Min (Archaeological and Anthropological Sciences, 2019)

Spermidine application alleviates salinity damage to antioxidant enzyme activity and gene expression in alfalfa - Yanhong Lou; Rui Guan; Mingjie Sun; Fei Han; Wei He; Hui Wang; Fupeng Song; Xiumin Cui; Yuping Zhuge (Ecotoxicology, 2018)

Neuregulin-1β Plays a Neuroprotective Role by Inhibiting the Cdk5 Signaling Pathway after Cerebral Ischemia-Reperfusion Injury in Rats - Rui Zhang; Cui Liu; Yaqing Ji; Lei Teng; Yunliang Guo (Journal of Molecular Neuroscience, 2018)

Spatial Distribution and Risk Assessment of Heavy Metals in Paddy Soils of Yongshuyu Irrigation Area from Songhua River Basin, Northeast China - Zhengwu Cui; Yang Wang; Na Zhao; Rui Yu; Guanghui Xu; Yong Yu (Chinese Geographical Science, 2018)

Association analysis between spatiotemporal variation of vegetation greenness and precipitation/temperature in the Yangtze River Basin (China) - Lifang Cui; Lunche Wang; Ramesh P. Singh; Zhongping Lai; Liangliang Jiang; Rui Yao (Environmental Science and Pollution Research, 2018)

Molecular simulation on competitive adsorption mechanism of CH4/CO2 on shale kerogen - Rui Song; Mengmeng Cui (Arabian Journal of Geosciences, 2018)

Use of Monte Carlo simulation to evaluate the efficacy of tigecycline and minocycline for the treatment of pneumonia due to carbapenemase-producing Klebsiella pneumoniae - Wentao Ni; Guobao Li; Jin Zhao; Junchang Cui; Rui Wang; Zhancheng Gao; Youning Liu (Infectious Diseases, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

HpaP, a novel regulatory protein with ATPase and phosphatase activity, contributes to full virulence in Xanthomonas campestris pv. campestris - Ping Cui; Rui‐Fang Li; Da‐Pei Zhang; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2018)
Summary The ability of the bacterial phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on the type III secretion system (T3SS). Proteins of the Xcc T3SS are encoded by hrp (hypersensitive response and pathogenicity) genes and whose expression is mainly controlled by the regulators HrpG and HrpX. Here, we describe the identification and characterization of a previously unknown regulatory protein ( named HpaP), which plays important role in hrp gene expression and virulence in Xcc . Clean deletion of hpaP demonstrated reduced virulence and HR (hypersensitive response) induction of Xcc and alterations in cell motility and stress tolerance. Global transcriptome analyses revealed that most hrp genes were down regulated in the hpaP mutant, suggesting HpaP positively regulates hrp genes. GUS activity assays implied that HpaP regulates the expression of hrp genes via controlling the expression of hrpX . Biochemical analyses revealed that HpaP protein had both ATPase and phosphatase activity. While further site‐directed mutagenesis of conserved residues in the PTP loop (a protein tyrosine phosphatase signature) of HpaP resulted in the loss of both phosphatase activity and regulatory activity in virulence and HR. Taken together, the findings identify a new regulatory protein that controls hrp gene expression and virulence in Xcc .

Fine-mapping and identifying candidate genes conferring resistance to Soybean mosaic virus strain SC20 in soybean - Adhimoolam Karthikeyan; Kai Li; Cui Li; Jinlong Yin; Na Li; Yunhua Yang; Yingpei Song; Rui Ren; Haijian Zhi; Junyi Gai (Theoretical and Applied Genetics, 2018)

Precipitation drives the biogeographic distribution of soil fungal community in Inner Mongolian temperate grasslands - Di Wang; Yichao Rui; Kai Ding; Xiaoyong Cui; Yanbin Hao; Li Tang; Zhe Pang; Biao Zhang; Shutong Zhou; Kui Wang; Yanfen Wang (Journal of Soils and Sediments, 2018)

Hepatotoxicity induced by intragastrically administrated with Gardenia decoction in mice - Yizhe Cui; Rui Sun; Qiuju Wang; Mengzhu Wang (Natural Product Research, 2017)

Estimating cadmium concentration in the edible part of Capsicum annuum using hyperspectral models - Ting Wang; Hong Wei; Cui Zhou; Yanwen Gu; Rui Li; Hongchun Chen; Wenchao Ma (Environmental Monitoring and Assessment, 2017)

Inheritance, fine-mapping, and candidate gene analyses of resistance to soybean mosaic virus strain SC5 in soybean - Adhimoolam Karthikeyan; Kai Li; Hua Jiang; Rui Ren; Cui Li; Haijian Zhi; Shouyi Chen; Junyi Gai (Molecular Genetics and Genomics, 2017)

Phosphorylation of histone H3 on Ser-10 by Aurora B is essential for chromosome condensation in porcine embryos during the first mitotic division - Changchao Chen; Zixiao Zhang; Panpan Cui; Yaya Liao; Yue Zhang; Lingyun Yao; Rong Rui; Shiqiang Ju (Histochemistry and Cell Biology, 2017)

Role of the SPS Gene Families in the Regulation of Sucrose Accumulation in Sugarcane - Dong-Liang Huang; Cui-Xian Qin; Yi-Yun Gui; Li-Han Zhao; Zhong-Liang Chen; Miao Wang; Yue Sun; Qing Liao; Yang-Rui Li; Prakash Lakshmanan (Sugar Tech, 2017)

Dietary Zinc Oxide Modulates Antioxidant Capacity, Small Intestine Development, and Jejunal Gene Expression in Weaned Piglets - Cui Zhu; Hang Lv; Zhuang Chen; Li Wang; Xiuju Wu; Zhongjian Chen; Weina Zhang; Rui Liang; Zongyong Jiang (Biological Trace Element Research, 2017)

Frequency and type of inheritable mutations induced by γ rays in rice as revealed by whole genome sequencing - Shan Li; Yun-chao Zheng; Hai-rui Cui; Hao-wei Fu; Qing-yao Shu; Jian-zhong Huang (Journal of Zhejiang University-SCIENCE B, 2016)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Transcriptome of High-Sucrose Sugarcane Variety GT35 - Dong-Liang Huang; Yi-Jing Gao; Yi-Yun Gui; Zhong-Liang Chen; Cui-Xian Qin; Miao Wang; Qing Liao; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Soil microbial community composition and its driving factors in alpine grasslands along a mountain elevational gradient - Hai-jun Cui; Gen-xu Wang; Yan Yang; Yang Yang; Rui-ying Chang; Fei Ran (Journal of Mountain Science, 2016)

Slope spectrum variation in a simulated loess watershed - Fayuan Li; Guoan Tang; Chun Wang; Lingzhou Cui; Rui Zhu (Frontiers of Earth Science, 2016)

Isolation and Expression Analysis of Sucrose Synthase Gene (ScSuSy4) from Sugarcane - Zhong-Liang Chen; Yi-Yun Gui; Cui-Xian Qin; Miao Wang; Qing Liao; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Sequence Characteristics and Phylogenetic Implications of the nrDNA Internal Transcribed Spacers (ITS) in Protospecies and Landraces of Sugarcane (Saccharum officinarum L.) - Cui-Feng Yang; Li-Tao Yang; Yang-Rui Li; Ge-Min Zhang; Chun-Ya Zhang; Wei-Zan Wang (Sugar Tech, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Metabolic responses to Lactobacillus plantarum contamination or bacteriophage treatment in Saccharomyces cerevisiae using a GC–MS-based metabolomics approach - Feng-Xia Cui; Rui-Min Zhang; Hua-Qing Liu; Yan-Feng Wang; Hao Li (World Journal of Microbiology and Biotechnology, 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Acclimation of Hydrilla verticillata to sediment anoxia in vegetation restoration in eutrophic waters - Juan Wu; Yanran Dai; Shengyang Rui; Naxin Cui; Fei Zhong; Shuiping Cheng (Ecotoxicology, 2015)

Inhibiting β-Amyloid-Associated Alzheimer’s Pathogenesis In Vitro and In Vivo by a Multifunctional Dimeric Bis(12)-hupyridone Derived from Its Natural Analogue - Shengquan Hu; Rui Wang; Wei Cui; Zaijun Zhang; Shinghung Mak; Daping Xu; Chunglit Choi; Karl Wahkeung Tsim; Paul R. Carlier; Mingyuen Lee; Yifan Han (Journal of Molecular Neuroscience, 2015)

Low Bone Mass is Associated with Stroke in Chinese Postmenopausal Women: The Chongqing Osteoporosis Study - Rui Zhou; Dong Liu; Rui Li; Shiming Zhou; Min Cui; Lin Chen; Huadong Zhou (Cell Biochemistry and Biophysics, 2015)

Brittleness index and seismic rock physics model for anisotropic tight-oil sandstone reservoirs - Xin-Rui Huang; Jian-Ping Huang; Zhen-Chun Li; Qin-Yong Yang; Qi-Xing Sun; Wei Cui (Applied Geophysics, 2015)

The role of visfatin on the regulation of inflammation and apoptosis in the spleen of LPS-treated rats - Ke Xiao; Wei-Hua Zou; Zhi Yang; Zia ur Rehman; Abdur Rahman Ansari; Huai-Rui Yuan; Ying Zhou; Lu Cui; Ke-Mei Peng; Hui Song (Cell and Tissue Research, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Genomewide identification and expression analysis of the ARF gene family in apple - XIAO-CUI LUO; MEI-HONG SUN; RUI-RUI XU; HUAI-RUI SHU; JIA-WEI WANG; SHI-ZHONG ZHANG (Journal of Genetics, 2014)

Production of low phytic acid rice by hairpin RNA- and artificial microRNA-mediated silencing of OsMIK in seeds - Wen-Xu Li; Jian-Zhong Huang; Hai-Jun Zhao; Yuan-Yuan Tan; Hai-Rui Cui; Yves Poirier; Qing-Yao Shu (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Upregulation of EHD2 after Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Ying Rui; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Maohong Cao (Journal of Molecular Neuroscience, 2014)

Introduction of two mutations into AroG increases phenylalanine production in Escherichia coli - Rui Ding; Lifei Liu; Xuhui Chen; Zhenhai Cui; Ao Zhang; Daming Ren; Lijun Zhang (Biotechnology Letters, 2014)

Seed-specific silencing of OsMRP5 reduces seed phytic acid and weight in rice - Wen-Xu Li; Hai-Jun Zhao; Wei-Qin Pang; Hai-Rui Cui; Yves Poirier; Qing-Yao Shu (Transgenic Research, 2014)

Modeling Carbon Fluxes Using Multi-Temporal MODIS Imagery and CO2 Eddy Flux Tower Data in Zoige Alpine Wetland, South-West China - Xiaoming Kang; Yanfen Wang; Huai Chen; Jianqing Tian; Xiaoyong Cui; Yichao Rui; Lei Zhong; Paul Kardol; Yanbin Hao; Xiangming Xiao (Wetlands, 2014)

A Comparative Study on the Effects of Excess Iodine and Herbs with Excess Iodine on Thyroid Oxidative Stress in Iodine-Deficient Rats - Tianshu Gao; Rui Shi; Tengche Qi; Huisi Yin; Lan Mei; Xiaoqing Han; Peng Cui (Biological Trace Element Research, 2014)

Characterization of OsMIK in a rice mutant with reduced phytate content reveals an insertion of a rearranged retrotransposon - Hai-Jun Zhao; Hai-Rui Cui; Xiu-Hong Xu; Yuan-Yuan Tan; Jun-Jie Fu; Guo-Zhen Liu; Yves Poirier; Qing-Yao Shu (Theoretical and Applied Genetics, 2013)

Association of Endothelin-converting Enzyme-1b C-338A Polymorphism with Increased Risk of Ischemic Stroke in Chinese Han Population - Rui Li; Min Cui; Jin Zhao; Mingming Yu; Zegang Ying; Shiming Zhou; Huadong Zhou (Journal of Molecular Neuroscience, 2013)

Up-regulation of SGTB is associated with neuronal apoptosis after neuroinflammation induced by lipopolysaccharide - Maohong Cao; Wei Xu; Jian Yu; Heyi Zheng; Xiang Tan; Lei Li; Ying Rui; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Tao Tao; et al. (Journal of Molecular Histology, 2013)

Up-regulated expression of Bnip3L after intracerebral hemorrhage in adult rats - Ying Rui; Kaifu Ke; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Guangwei Zhao; Yilu Gao; Maohong Cao (Journal of Molecular Histology, 2013)

Increased Expression of Small Heat Shock Protein αB-crystallin After Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Lei Li; Ying Rui; Heyi Zheng; Xiang Tan; Wei Xu; Jianhua Cao; Jian Xu; Gang Cui; Guangfei Xu; Maohong Cao (Journal of Molecular Neuroscience, 2013)

Effects of grazing on CO2 balance in a semiarid steppe: field observations and modeling - Xiaoming Kang; Yanbin Hao; Xiaoyong Cui; Huai Chen; Changsheng Li; Yichao Rui; Jianqing Tian; Paul Kardol; Lei Zhong; Jinzhi Wang; Yanfen Wang (Journal of Soils and Sediments, 2013)

Upregulation of CBLL1 in rat brain cortex after lipopolysaccharide treated - Maohong Cao; Heyi Zheng; Xiang Tan; Wei Xu; Ying Rui; Lei Li; Xiaofei Liu; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Kaifu Ke; et al. (Journal of Molecular Histology, 2013)

The binding characteristics of the interaction between 3-(2-cyanoethyl) cytosine and human serum albumin - Feng-Ling Cui; Guang-Quan Hui; Rui-Na Huo; Gui-Rong Qu (Molecular Biology Reports, 2012)

Effects of warming and grazing on soil N availability, species composition, and ANPP in an alpine meadow - Shiping Wang; Jichuang Duan; Guangping Xu; Yanfen Wang; Zhenhua Zhang; Yichao Rui; Caiyun Luo; Burenbayin Xu; Xiaoxue Zhu; Xiaofeng Chang; Xiaoyong Cui; Haishan Niu; et al. (Ecology, 2012)
Uncertainty about the effects of warming and grazing on soil nitrogen (N) availability, species composition, and aboveground net primary production (ANPP) limits our ability to predict how global carbon sequestration will vary under future warming with grazing in alpine regions. Through a controlled asymmetrical warming (1.2/1.7°C during daytime/nighttime) with a grazing experiment from 2006 to 2010 in an alpine meadow, we found that warming alone and moderate grazing did not significantly affect soil net N mineralization. Although plant species richness significantly decreased by 10% due to warming after 2008, we caution that this may be due to the transient occurrence or disappearance of some rare plant species in all treatments. Warming significantly increased graminoid cover, except in 2009, and legume cover after 2008, but reduced non‐legume forb cover in the community. Grazing significantly decreased cover of graminoids and legumes before 2009 but increased forb cover in 2010. Warming significantly increased ANPP regardless of grazing, whereas grazing reduced the response of ANPP to warming. N addition did not affect ANPP in both warming and grazing treatments. Our findings suggest that soil N availability does not determine ANPP under simulated warming and that heavy grazing rather than warming causes degradation of the alpine meadows.

Influences of free-air CO2 enrichment (FACE), nitrogen fertilizer and crop residue incorporation on CH4 emissions from irrigated rice fields - Baohua Xie; Zaixing Zhou; Baoling Mei; Xunhua Zheng; Haibo Dong; Rui Wang; Shenghui Han; Feng Cui; Yinghong Wang; Jianguo Zhu (Nutrient Cycling in Agroecosystems, 2012)

Study on antitumor activity of metal-based diketone complexes - Kaizhi Zhang; Shusen Cui; Jingjing Wang; Xiaohong Wang; Rui Li (Medicinal Chemistry Research, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Immobilization of foreign protein into polyhedra of Bombyx mori nucleopolyhedrovirus (BmNPV) - Xing-wei Xiang; Rui Yang; Lin Chen; Xiao-long Hu; Shao-fang Yu; Cui-ping Cao; Xiao-feng Wu (Journal of Zhejiang University-SCIENCE B, 2012)

Comparative proteomic and radiobiological analyses in human lung adenocarcinoma cells - Rui Wei; Yingjin Zhang; Liangfang Shen; Wuzhong Jiang; Cui Li; Meizuo Zhong; Yun Xie; Dingyi Yang; Lili He; Qing Zhou (Molecular and Cellular Biochemistry, 2012)

Effects of Lanthanum Chloride Administration on Detouring Learning in Chicks - Yi Che; Rui Xing; Yufang Zhu; Yonghua Cui; Xinghong Jiang (Biological Trace Element Research, 2011)

Modeling impacts of climate change on carbon dynamics in a steppe ecosystem in Inner Mongolia, China - Xiaoming Kang; Yanbin Hao; Changsheng Li; Xiaoyong Cui; Jinzhi Wang; Yichao Rui; Haishan Niu; Yanfen Wang (Journal of Soils and Sediments, 2011)

Zebrafish Ubc13 is required for Lys63-linked polyubiquitination and DNA damage tolerance - Jie Li; Rui Wen; Parkeer Andersen; Yuping Liang; Qing Li; Wei Xiao; Zongbin Cui (Molecular and Cellular Biochemistry, 2010)

Salicylic Acid Reduces Napropamide Toxicity by Preventing Its Accumulation in Rapeseed (Brassica napus L.) - Jing Cui; Rui Zhang; Guo Lin Wu; Hong Mei Zhu; Hong Yang (Archives of Environmental Contamination and Toxicology, 2010)

Preparation, Safety, Pharmacokinetics, and Pharmacodynamics of Liposomes Containing Brucea javanica Oil - Yanxia Cui; Zimei Wu; Xiaoxu Liu; Rui Ni; Xuanxuan Zhu; Lulu Ma; Jianping Liu (AAPS PharmSciTech, 2010)

Isolation, Functional Characterization, and Expression Pattern of a Vacuolar Na+/H+ Antiporter Gene TrNHX1 from Trifolium repens L. - Rui Tang; Cui Li; Kai Xu; Yanhua Du; Tao Xia (Plant Molecular Biology Reporter, 2010)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Tumor-inhibitory and liver-protective effects of Phellinus igniarius extracellular polysaccharides - Wei Dong; Li Ning; Wei-dong Lu; Cui-cui Li; Rui-peng Chen; Xiao-ning Jia; Lin Wang; Li-zhong Guo (World Journal of Microbiology and Biotechnology, 2009)

Agronomic and morphological characterization of Agrobacterium-transformed Bt rice plants - Qing-yao Shu; Hai-rui Cui; Gong-yin Ye; Dian-xing Wu; Ying-wu Xia; Ming-wei Gao; Illimar Altosaar (Euphytica, 2002)